Light absorbing anisotropic layer, optical film, viewing angle control system, and image display device
Patent Information
- Application Number
- CN202280033820.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-14
- Filing Date
- 2022-04-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-04-28
AI Technical Summary
[0039]根据本发明,能够提供一种光吸收各向异性层以及使用该光吸收各向异性层的光学膜、视角控制系统及图像显示装置,所述光吸收各向异性层在从所期望的方向的图像的视觉辨认度高且能够充分遮断从除其以外的方向的图像的视角控制系统中使用。
Smart Images

Figure QLYQS_1 
Figure BDA0004537036500000101 
Figure BDA0004537036500000121
Abstract
Description
Technical Field
[0001] This invention relates to a light absorption anisotropic layer, an optical film, a viewing angle control system, and an image display device. Background Technology
[0002] To prevent peeping or viewing angle control of image display devices, a technique is known that simultaneously uses a light-absorbing anisotropic layer having an absorption axis in the thickness direction. For example, Patent Document 1 discloses a viewing angle control system that contains a dichroic material and has a polarizer (light-absorbing anisotropic layer) with an absorption axis forming an angle of 0° to 45° with the normal to the film surface.
[0003] Patent documents
[0004] Patent Document 1: Japanese Patent Application Publication No. 2009-145776 Summary of the Invention
[0005] The technical problem to be solved by the invention
[0006] Regarding view control systems, for example in automotive applications, there are situations where the image is not easily visible from the direction of the driver or front passenger, i.e., from the direction from which information is obtained through accurate and rapid visual recognition. On the other hand, the image is only slightly visible from the direction of the window glass, i.e., from the direction from which the image is to be eliminated.
[0007] Therefore, in applications that transmit light in a specific direction, angle control is extremely important. In order to cut off light transmission at angles other than a specific direction, it is also extremely important that the light absorption anisotropic layer has sufficient absorption.
[0008] Based on their research on the viewing angle control system described in Patent Document 1, the inventors discovered that while the visual recognition of the image is good when viewed from the direction from which the image is to be seen (the desired direction), the image cannot be adequately obscured when viewed from other directions.
[0009] Therefore, the objective of this invention is to provide a light-absorbing anisotropic layer and an optical film, a viewing angle control system, and an image display device using the light-absorbing anisotropic layer, wherein the light-absorbing anisotropic layer is used in a viewing angle control system that provides high visual recognition of an image from a desired direction and can adequately block images from other directions.
[0010] The inventors have discovered that the above-mentioned problems can be solved by the following structure.
[0011] [1] A light-absorbing anisotropic layer, formed of a liquid crystal composition containing a liquid crystal compound, a dichroic substance and an alignment agent, wherein,
[0012] The content of the dichroic substance is 8.0% by mass or more relative to the total solid content of the liquid crystal composition.
[0013] The angle θ between the transmittance central axis of the light-absorbing anisotropic layer and the normal direction of the surface of the light-absorbing anisotropic layer is greater than 5° and less than 80°.
[0014] [2] According to the light absorption anisotropic layer described in [1], wherein,
[0015] The content of the dichroic substance is 13.0% by mass or more relative to the total solid content of the liquid crystal composition.
[0016] [3] According to the light absorption anisotropic layer described in [1] or [2], wherein,
[0017] Liquid crystal compounds are liquid crystal compounds that exhibit thermotropic properties.
[0018] [4] According to the light absorption anisotropic layer described in [3], wherein,
[0019] The orientation agent is an orientation agent that can set the phase transition reduction temperature ΔTF, as defined by the following formula (TF), to -10.0℃ to -0.1℃.
[0020] ΔTF=T1-T2……(TF)
[0021] In the above formula (TF),
[0022] T1 represents the phase transition temperature of the liquid and liquid crystal in a liquid crystal composition t1 containing a thermotropic liquid crystal compound and a dichroic substance but without an alignment agent.
[0023] T2 represents the phase transition temperature of the liquid and the liquid crystal in a mixture t2 containing 2.0 parts by mass of an alignment agent relative to 100 parts by mass of the liquid crystal composition t1.
[0024] [5] The light-absorbing anisotropic layer according to any one of [1] to [4], wherein,
[0025] The content of the orientation agent satisfies the following formula (C).
[0026] 0.010≤Ct / FT≤0.020……(C)
[0027] In this context, in equation (C) above,
[0028] Ct represents the content (mass%) of the alignment agent relative to the total solid content of the liquid crystal composition.
[0029] FT represents the film thickness (μm) of the light-absorbing anisotropic layer.
[0030] [6] The light-absorbing anisotropic layer according to any one of [1] to [5], wherein,
[0031] The orientation agent is a compound represented by formula (B1) or (B2) as described below.
[0032] [7] An optical film having a light-absorbing anisotropic layer as described in any one of [1] to [6] and an orientation film made of polyvinyl alcohol or polyimide disposed on the light-absorbing anisotropic layer.
[0033] [8] A viewing angle control system having a polarizer having an absorption axis in an in-plane direction and a light-absorbing anisotropic layer as described in any one of [1] to [6] or an optical film as described in [7].
[0034] [9] An image display device having a display element and the viewing angle control system described in [8]
[0035] The viewing angle control system is configured on at least one main surface of the display element.
[0036]
[10] The image display device according to [9], wherein,
[0037] The light absorption anisotropy layer of the viewing angle control system is positioned closer to the visual recognition side than the polarizer of the viewing angle control system.
[0038] Invention Effects
[0039] According to the present invention, a light-absorbing anisotropic layer and an optical film, a viewing angle control system, and an image display device using the light-absorbing anisotropic layer are provided. The light-absorbing anisotropic layer is used in a viewing angle control system that provides high visual recognition of an image from a desired direction and can adequately block images from other directions. Detailed Implementation
[0040] The present invention will now be described in detail.
[0041] The following description of the constituent elements is based on a representative embodiment of the present invention, but the present invention is not limited to such embodiments.
[0042] In addition, in this specification, the numerical range indicated by “~” represents the range to be included by the values recorded before and after “~” as the lower limit and upper limit values.
[0043] Furthermore, in this specification, parallel and orthogonal refer to the range of parallel ±5° and orthogonal ±5°, respectively, rather than parallel and orthogonal in the strict sense.
[0044] Furthermore, in this specification, the concepts of liquid crystal compositions and liquid crystal compounds also include compositions and compounds that no longer exhibit liquid crystal properties due to curing or other processes.
[0045] Furthermore, in this specification, each component may be used alone with one equivalent substance, or two or more substances may be used simultaneously. When two or more substances are used simultaneously for each component, unless otherwise specified, the content of that component refers to the total content of the substances used simultaneously.
[0046] Furthermore, in this specification, "(meth)acrylate" is a designation for "acrylate" or "methacrylate", "(meth)acrylic acid" is a designation for "acrylic acid" or "methacrylic acid", and "(meth)acryloyl" is a designation for "acryloyl" or "methacryloyl".
[0047] [Substituent W]
[0048] In this specification, the substituent W represents the following groups.
[0049] Examples of substituents W include halogen atoms, alkyl groups with 1 to 20 carbon atoms, haloalkyl groups with 1 to 20 carbon atoms, cycloalkyl groups with 1 to 20 carbon atoms, alkylcarbonyl groups with 1 to 10 carbon atoms, alkoxycarbonyl groups with 1 to 10 carbon atoms, alkylcarbonyloxy groups with 1 to 10 carbon atoms, alkylamino groups with 1 to 10 carbon atoms, alkylaminocarbonyl groups, alkoxy groups with 1 to 20 carbon atoms, alkenyl groups with 1 to 20 carbon atoms, alkynyl groups with 1 to 20 carbon atoms, aryl groups with 1 to 20 carbon atoms, and heterocyclic groups (which can also be called heterocyclic groups). (group), cyano, hydroxy, nitro, carboxyl, aryloxy, silyloxy, heterocyclic, acyloxy, carbamoyloxy, alkoxycarbonyloxy, aryloxycarbonyloxy, amino (including aniline), ammonium, acylamino, aminocarbonylamino, alkoxycarbonylamino, aryloxycarbonylamino, aminosulfonylamino, alkyl or arylsulfonylamino, mercapto, alkylthio, arylthio, heterocyclic thio, aminosulfonyl, sulfonyl, alkyl or arylsulfinyl, alkyl or arylsulfonyl, acyl, aryloxycarbonyl, alkoxycarbonyl, carbamoyl, aryl or heteroaryl azo, imide, phosphinyl, oxophosphinyl, oxophosphinyloxy, oxophosphinylamino, phosphonyl, silyl, hydrazyl, urea, borate (-B(OH)2), phosphate (-OPO(OH)2), sulfate (-OSO3H), and other known substituents.
[0050] In addition, details regarding the substituents are described in paragraph
[0023] of Japanese Patent Application Publication No. 2007-234651.
[0051] Furthermore, the substituent W can also be a group represented by the following formula (W1).
[0052] [Chemical Formula 1]
[0053] *-LW-SPW-Q (W1)
[0054] In formula (W1), LW represents a single bond or a divalent linker, SPW represents a divalent spacer, Q represents Q1 or Q2 in the following formula (LC), and * represents the bonding position.
[0055] Examples of divalent linkers represented by LW include -O- and -(CH2). g -、-(CF2) g -、-Si(CH3)2-、-(Si(CH3)2O) g -、-(OSi(CH3)2) g -(g represents an integer from 1 to 10.), -N(Z)-, -C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)2-C(Z')2-, -C(O)-, -OC(O)-, -C(O)O-, -OC(O)O-, -N(Z)C( O)-, -C(O)N(Z)-, -C(Z)=C(Z')-C(O)O-, -OC(O)-C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)=C(Z')-C(O)N(Z”)-, -N(Z”)-C(O)-C (Z)=C(Z')-, -C(Z)=C(Z')-C(O)-S-, -SC(O)-C(Z)=C(Z')-, -C(Z)=NN=C(Z')- (Z, Z', Z" independently represent hydrogen, alkyl, cycloalkyl, aryl, cyano or halogen atoms with 1 to 4 carbon atoms.), -C≡C-, -N=N-, -S-, -S(O)-, -S(O)(O)-, -(O)S(O)O-, -O(O)S(O)O-, -SC(O)- and -C(O)S-, etc. LW can be a group formed by combining two or more of these groups (hereinafter also abbreviated as "LC").
[0056] Examples of divalent spacer groups represented by SPW include straight-chain, branched, or cyclic alkylene groups or heterocyclic groups with 1 to 20 carbon atoms, which have 1 to 50 carbon atoms.
[0057] The carbon atoms of the aforementioned alkylene and heterocyclic groups can be replaced by -O-, -Si(CH3)2-, or -(Si(CH3)2O). g -、-(OSi(CH3)2) g-(g represents an integer from 1 to 10.), -N(Z)-, -C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)2-C(Z')2-, -C(O)-, -OC(O)-, -C(O)O-, -OC(O)O-, -N(Z)C( O)-, -C(O)N(Z)-, -C(Z)=C(Z')-C(O)O-, -OC(O)-C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)=C(Z')-C(O)N(Z”)-, -N(Z”)-C(O)-C( Z)=C(Z')-, -C(Z)=C(Z')-C(O)-S-, -SC(O)-C(Z)=C(Z')-, -C(Z)=NN=C(Z')- (Z, Z', Z" independently represent hydrogen, alkyl, cycloalkyl, aryl, cyano or halogen atoms with 1 to 4 carbon atoms.), -C≡C-, -N=N-, -S-, -C(S)-, -S(O)-, -SO2-, -(O)S(O)O-, -O(O)S(O)O-, -SC(O)- and -C(O)S-, group substitution formed by combining two or more of these groups (hereinafter also abbreviated as "SP-C").
[0058] The hydrogen atoms of the aforementioned alkylene groups and heterocyclic groups can be halogen atoms, cyano groups, or -Z groups. H -OH, -OZ H -COOH, -C(O)Z H -C(O)OZ H -OC(O)Z H -OC(O)OZ H -NZ H Z H '、-NZ H C(O)Z H '、-NZ H C(O)OZ H '、-C(O)NZ H Z H '、-OC(O)NZ H Z H '、-NZ H C(O)NZ H 'OZ H "、-SH、-SZ H and -C(S)Z H -C(O)SZ H -SC(O)Z H Replace (hereinafter, also abbreviated as "SP-H"). Here, Z H Z H'Represents an alkyl group, a haloalkyl group, or a -L-CL group having 1 to 10 carbon atoms (L represents a single bond or a divalent linker. Specific examples of divalent linkers are the same as those for LW and SPW mentioned above. CL represents a crosslinking group, which can be represented by Q1 or Q2 in the following formula (LC), preferably crosslinking groups represented by formulas (P1) to (P30) mentioned below.)
[0059] [Light Absorption Anisotropic Layer]
[0060] The light absorption anisotropic layer of the present invention is a light absorption anisotropic layer formed from a liquid crystal composition containing a liquid crystal compound, a dichroic substance, and an alignment agent. That is, it is preferably a light absorption anisotropic layer formed by fixing the alignment state of the liquid crystal compound and the dichroic substance contained in the liquid crystal composition containing the liquid crystal compound, the dichroic substance, and the alignment agent.
[0061] Furthermore, in the light-absorbing anisotropic layer of the present invention, the content of dichroic material is 8.0% by mass or more relative to the total solid content of the liquid crystal composition.
[0062] Furthermore, in the light-absorbing anisotropic layer of the present invention, the angle θ (hereinafter also referred to as "transmittance center axis angle θ") formed by the transmittance central axis of the light-absorbing anisotropic layer and the normal direction of the surface of the light-absorbing anisotropic layer is 5° or more and less than 80°.
[0063] Here, the transmittance center axis refers to the direction in which transmittance is highest when the tilt angle and tilt direction relative to the normal direction of the light absorption anisotropic layer surface are changed to measure transmittance.
[0064] Furthermore, the aforementioned transmittance central axis angle θ can be determined as follows: using wavelengths within the absorption region of the dichroic material (e.g., the visible wavelength region), polarized light parallel to the direction of the orthogonal projection of the transmittance central axis of the light-absorbing anisotropic layer (hereinafter also referred to as "φ1") is incident on the light-absorbing anisotropic layer, and the light-absorbing anisotropic layer is tilted from the normal direction (θ = 0°) to in-plane (θ = -75° to 75°) to measure the transmittance, thereby determining the direction with the highest transmittance.
[0065] In this invention, by using a light-absorbing anisotropic layer formed from a liquid crystal composition containing a liquid crystal compound, a dichroic substance, and an alignment agent, where the content of the dichroic substance is 8.0% or more by mass relative to the total solid content of the liquid crystal composition and the transmittance central axis angle θ is 5° or more and less than 80°, it is possible to produce a viewing angle control system that provides high visual recognition of images from the desired direction and can adequately block images from other directions.
[0066] The exact reasons are unclear, but the inventor speculates as follows.
[0067] First, in the light-absorbing anisotropic layer of the present invention, the transmittance central axis angle θ is adjusted by tilting and aligning the liquid crystal compound and the dichroic material.
[0068] Furthermore, it is believed that sufficient absorption is achieved due to the high content of dichroic substances in the light-absorbing anisotropic layer of the present invention.
[0069] However, it is believed that in light-absorbing anisotropic layers with a high content of dichroic material, even if the transmittance central axis angle θ is greater than 5° and less than 80°, uneven light transmission and absorption will occur if there is a deviation in the tilt angle of the liquid crystal compound and the dichroic material.
[0070] Therefore, in this invention, by using a liquid crystal composition that includes not only liquid crystal compounds and dichroic substances but also an alignment agent to form a light-absorbing anisotropic layer, the tilt angle near the interface with the lower layer side of the light-absorbing anisotropic layer is controlled, thus it is believed that both visual recognition from the desired direction and light-blocking properties from other directions can be achieved.
[0071] In this invention, the transmittance center axis angle θ is preferably 5° or more and less than 45°, more preferably 5° or more and less than 35°, further preferably 5° or more and less than 35°, especially preferably more than 5° and less than 35°, and most preferably more than 10° and less than 35°.
[0072] Regarding techniques for orienting dichroic materials in a desired direction, reference can be made to fabrication techniques for polarizers utilizing dichroic materials or fabrication techniques for guest-host liquid crystal cells.
[0073] For example, the techniques used in the manufacturing method of the dichroic polarizing light element described in Japanese Patent Application Publication No. 11-305036 or Japanese Patent Application Publication No. 2002-90526, and the manufacturing method of the guest-host type liquid crystal display device described in Japanese Patent Application Publication No. 2002-99388 or Japanese Patent Application Publication No. 2016-27387, can also be used to manufacture the light absorption anisotropic layer of the present invention.
[0074] Specifically, when using the guest-host type liquid crystal cell technology, a dichroic substance that becomes the guest and a rod-shaped liquid crystal compound that becomes the host liquid crystal are mixed. While the host liquid crystal is oriented, the molecules of the dichroic substance are oriented and their orientation is fixed along with the orientation of its liquid crystal molecules. This allows the light absorption anisotropic layer of the present invention to be fabricated.
[0075] To prevent changes in the light absorption characteristics of the anisotropic light absorption layer of the present invention due to the usage environment, it is preferable to fix the orientation of the dichroic material by forming chemical bonds. For example, the orientation can be fixed by polymerizing the main liquid crystal, the dichroic material, and polymerizable components added as needed.
[0076] The transmittance (referring to the transmittance at a wavelength of 550 nm, hereinafter the same) of the light-absorbing anisotropic layer of the present invention, tilted at 30° from the transmittance center axis, is preferably 60% or less, more preferably 50% or less, and even more preferably 45% or less. This improves the contrast between the illuminance at the transmittance center and in directions deviating from the transmittance center, and sufficiently reduces the viewing angle.
[0077] The transmittance of the central axis of the light-absorbing anisotropic layer of the present invention is preferably 65% or more, more preferably 75% or more, and even more preferably 80% or more. This improves the illuminance at the viewing angle center of the image display device and enhances visual clarity.
[0078] From the perspective of enabling the hue in the positive direction to be neutral, the orientation degree of the light-absorbing anisotropic layer of the present invention preferably satisfies 0.93 or more at 420 nm.
[0079] Here, the hue control of optical films containing dichroic substances is typically achieved by adjusting the amount of dichroic substance added to the film. However, it is known that simply adjusting the amount of dichroic substance added cannot set the hue in both the front and tilted directions to a neutral state. The reason why the hue in both the front and tilted directions cannot be set to a neutral state is due to the low orientation degree at 420nm. By setting the orientation degree of 420nm to a high orientation degree, the hue in both the front and tilted directions can be set to neutral.
[0080] Considering the ease with which the transmittance tilted by 30° from the transmittance center axis and the transmittance of the transmittance center axis can be adjusted within the aforementioned range, the light absorption anisotropic layer of the present invention can be stacked with multiple light absorption anisotropic layers or stacked with phase difference layers that have different transmittance center axes.
[0081] By stacking multiple anisotropic light absorption layers with different central axes of transmittance, the width of the high transmittance region can be adjusted.
[0082] Furthermore, by controlling the phase difference value and optical axis direction during the stacking of the retardation layer, the transmission performance and light-blocking performance can be controlled. Positive A-plate, negative A-plate, positive C-plate, negative C-plate, B-plate, O-plate, etc., can be used as the retardation layer. From the viewpoint of making the viewing angle control system thinner, the thickness of the retardation layer is preferably thinner without compromising optical properties, mechanical properties, and manufacturing applicability. Specifically, it is preferably 1 to 150 μm, more preferably 1 to 70 μm, and even more preferably 1 to 30 μm.
[0083] [Liquid Crystal Composition]
[0084] The light-absorbing anisotropic layer of the present invention is formed from a liquid crystal composition containing a liquid crystal compound, a dichroic substance and an alignment agent.
[0085] Furthermore, the liquid crystal composition may contain solvents, polymerization initiators, polymerizable compounds, surface modifiers, and other additives.
[0086] The following is a description of each component.
[0087] <Liquid Crystal Compounds>
[0088] The liquid crystal composition contains a liquid crystal compound. By containing a liquid crystal compound, the precipitation of dichroic substances can be suppressed while simultaneously enabling the dichroic substances to be oriented with a high degree of orientation.
[0089] Furthermore, the liquid crystal compounds contained in liquid crystal compositions can generally be classified into rod-shaped and disc-shaped types according to their shape.
[0090] Furthermore, the liquid crystal compound is preferably a liquid crystal compound that does not exhibit dichroism in the visible region.
[0091] Furthermore, in the following description, "the orientation degree of the formed light absorption anisotropic layer becomes higher" is also referred to as "the effect of the present invention is more superior".
[0092] As a liquid crystal compound, either a low-molecular-weight liquid crystal compound or a high-molecular-weight liquid crystal compound can be used.
[0093] Here, "low molecular weight liquid crystal compound" refers to a liquid crystal compound that does not have repeating units in its chemical structure.
[0094] Furthermore, "high molecular weight liquid crystal compounds" refers to liquid crystal compounds that have repeating units in their chemical structure.
[0095] As a low-molecular-weight liquid crystal compound, for example, the liquid crystal compound described in Japanese Patent Application Publication No. 2013-228706 can be cited.
[0096] Examples of polymeric liquid crystal compounds include, for instance, the thermotropic liquid crystal polymer described in Japanese Patent Application Publication No. 2011-237513. Furthermore, the polymeric liquid crystal compound may have crosslinking groups (e.g., acryloyl and methacryloyl groups) at its ends.
[0097] From the perspective of easily demonstrating the effects of the present invention, the liquid crystal compound is preferably a rod-shaped liquid crystal compound, and more preferably a polymeric liquid crystal compound.
[0098] Furthermore, from the perspective of easily demonstrating the effects of the present invention, the liquid crystal compound is preferably a liquid crystal compound exhibiting thermotropic properties (hereinafter also referred to as "thermotropic liquid crystal"). Additionally, thermotropic liquid crystal refers to a liquid crystal that exhibits a transition to a liquid crystal phase through temperature changes.
[0099] Liquid crystal compounds can be used alone or in combination with two or more compounds.
[0100] From the viewpoint of achieving better results with the present invention, the liquid crystal compound preferably comprises a high molecular weight liquid crystal compound, and more preferably comprises both a high molecular weight liquid crystal compound and a low molecular weight liquid crystal compound.
[0101] The liquid crystal compound preferably contains a liquid crystal compound or a polymer thereof represented by formula (LC). The liquid crystal compound or its polymer represented by formula (LC) is a compound exhibiting liquid crystal properties. The liquid crystal properties can be a nematic phase or a smectic phase, or both a nematic phase and a smectic phase, preferably at least a nematic phase.
[0102] As a smectic phase, it can be a higher-order smectic phase. The higher-order smectic phases referred to here are smectic B phase, smectic D phase, smectic E phase, smectic F phase, smectic G phase, smectic H phase, smectic I phase, smectic J phase, smectic K phase, and smectic L phase, among which, smectic B phase, smectic F phase, and smectic I phase are preferred.
[0103] If the smectic liquid crystal phase exhibited by the liquid crystal compound is one of these higher-order smectic liquid crystal phases, then a light absorption anisotropic layer with a higher degree of orientation order can be fabricated. Furthermore, such a light absorption anisotropic layer fabricated from a higher-order smectic liquid crystal phase with a high degree of orientation order is a layer in which Bragg peaks originating from higher-order structures such as hexagonal or crystalline phases are obtained in X-ray diffraction measurements. The aforementioned Bragg peaks refer to peaks originating from the planar periodic structure of molecular orientation. According to the liquid crystal composition of the present invention, a periodic interval of [missing information] can be obtained. Anisotropic light absorption layer.
[0104] [Chemical Formula 2]
[0105] Q1-S1-MG-S2-Q2 (LC)
[0106] In formula (LC), Q1 and Q2 independently represent hydrogen atoms, halogen atoms, straight-chain, branched, or cyclic alkyl groups with 1 to 20 carbon atoms, alkoxy groups with 1 to 20 carbon atoms, alkenyl groups with 1 to 20 carbon atoms, alkynyl groups with 1 to 20 carbon atoms, aryl groups with 1 to 20 carbon atoms, heterocyclic groups (also referred to as heterocyclic groups), cyano groups, hydroxyl groups, nitro groups, carboxyl groups, aryloxy groups, silyloxy groups, heterocyclic groups, acyloxy groups, carbamoyloxy groups, alkoxycarbonyloxy groups, aryloxycarbonyloxy groups, amino groups (including aniline groups), ammonium groups, amide groups, aminocarbonylamino groups, alkoxycarbonylamino groups, aryloxycarbonylamino groups, aminosulfonylamino groups, alkyl or arylsulfonylamino groups, mercaptoalkylthio groups, arylthio groups, heterocyclic thio groups, aminosulfonyl groups, sulfonyl groups, alkyl or arylsulfinyl groups, alkyl or arylsulfonyl groups. Acyl, aryloxycarbonyl, alkoxycarbonyl, carbamoyl, aryl or heterocyclic azo, imide, phosphin, oxyphosphinyl, oxyphosphinyloxy, oxyphosphinylamino, phosphonyl, silyl, hydrazine, urea, borate (-B(OH)2), phosphate (-OPO(OH)2), sulfate (-OSO3H) or a crosslinking group represented by the following formulas (P1) to (P-30), wherein at least one of Q1 and Q2 is preferably a crosslinking group represented by the following formula.
[0107] [Chemical Formula 3]
[0108]
[0109] In equations (P-1) to (P-30), R P This refers to hydrogen atoms, halogen atoms, straight-chain, branched, or cyclic alkyl groups with 1 to 10 carbon atoms, haloalkyl groups with 1 to 20 carbon atoms, alkoxy groups with 1 to 20 carbon atoms, alkenyl groups with 1 to 20 carbon atoms, alkynyl groups with 1 to 20 carbon atoms, aryl groups with 1 to 20 carbon atoms, and heterocyclic groups (also known as heterocyclic groups). (group), cyano, hydroxy, nitro, carboxyl, aryloxy, siloxy, heterocyclic, acyloxy, carbamoyloxy, alkoxycarbonyloxy, aryloxycarbonyloxy, amino (including aniline), ammonium, acylamino, aminocarbonylamino, alkoxycarbonylamino, aryloxycarbonylamino, aminosulfonylamino, alkyl or arylsulfonylamino, mercapto, alkylthio, arylthio, heterocyclic thio, aminosulfonyl, sulfonyl, alkyl or arylsulfinyl, alkyl or arylsulfonyl, acyl, aryloxycarbonyl, alkoxycarbonyl, carbamoyl, aryl or heterocyclic azo, imide, phosphinyl, oxophosphinyl, oxophosphinyloxy, oxophosphinylamino, phosphonyl, silylalkyl, hydrazyl, urea, borate (-B(OH)2), phosphate (-OPO(OH)2) or sulfate (-OSO3H), multiple R P They can be the same, or they can be completely different.
[0110] Preferred crosslinking groups include free radical polymerizable groups and cationic polymerizable groups. For free radical polymerizable groups, preferred groups are vinyl groups represented by formula (P-1), butadiene groups represented by formula (P-2), (meth)acrylic acid groups represented by formula (P-4), (meth)acrylamide groups represented by formula (P-5), vinyl acetate groups represented by formula (P-6), fumarate groups represented by formula (P-7), styrene groups represented by formula (P-8), vinylpyrrolidone groups represented by formula (P-9), maleic anhydride groups represented by formula (P-11), or maleimide groups represented by formula (P-12). For cationic polymerizable groups, preferred groups are vinyl ether groups represented by formula (P-18), epoxy groups represented by formula (P-19), or oxobutyl groups represented by formula (P-20).
[0111] In equation (LC), S1 and S2 independently represent divalent spacer bases. Preferred embodiments of S1 and S2 can be exemplified by structures identical to SPW in equation (W1) above, so their description is omitted.
[0112] In formula (LC), MG represents the mesocrystalline group described later. The mesocrystalline group represented by MG refers to the group that represents the main framework of liquid crystal molecules that contribute to the formation of liquid crystals. Liquid crystal molecules exhibit liquid crystal properties in an intermediate state (mesocrystalline phase) between the crystalline state and the isotropic liquid state. There are no particular limitations regarding the mesocrystalline group; for example, one can refer to the description in "Flussige Kristallein Tabellen II" (VEB Deutsche Verlag fur Grundstoff Industrie, Leipzig, 1984), especially pages 7-16, and the description in "Liquid Crystal Handbook Editorial Committee, Liquid Crystal Handbook" (Maruzen, 2000), especially Chapter 3.
[0113] The mesocrystalline group represented by MG preferably contains 2 to 10 cyclic structures, more preferably 3 to 7.
[0114] Specific examples of cyclic structures include aromatic hydrocarbon groups, heterocyclic groups, and alicyclic groups.
[0115] From the viewpoints of liquid crystal manifestation, liquid crystal phase transition temperature adjustment, raw material availability and synthetic suitability, and from the viewpoint of better effects of the present invention, the mesocrystalline group represented by MG is preferably a group represented by the following formula (MG-A) or the following formula (MG-B), and more preferably a group represented by formula (MG-B).
[0116] [Chemical Formula 4]
[0117]
[0118] In formula (MG-A), A1 is a divalent group selected from the group consisting of aromatic hydrocarbon groups, heterocyclic groups, and alicyclic groups. These groups can be substituted by substituents such as W.
[0119] The divalent group represented by A1 is preferably a 4- to 15-membered ring. Furthermore, the divalent group represented by A1 can be a monocyclic ring or a fused ring.
[0120] * indicates the bonding position with S1 or S2.
[0121] Examples of divalent aromatic hydrocarbon groups represented by A1 include phenylene, naphthylene, fluorene-diyl, anthracene-diyl, and tetraphenyl-diyl. From the perspective of the diversity of mesocrystalline framework design or the availability of raw materials, phenylene and naphthylene are preferred.
[0122] The divalent heterocyclic group represented by A1 can be either aromatic or non-aromatic, but from the viewpoint of further improving the degree of orientation, a divalent aromatic heterocyclic group is preferred.
[0123] Examples of atoms other than carbon that constitute a divalent aromatic heterocyclic group include nitrogen, sulfur, and oxygen atoms. In cases where an aromatic heterocyclic group has multiple atoms constituting the ring (excluding carbon), these atoms can be the same or different.
[0124] Specific examples of divalent aromatic heterocyclic groups include, for example, pyridinyl (pyridin-diyl), pyridazin-diyl, imidazole-diyl, thiophenyl (thiophen-diyl), quinolineyl (quinoline-diyl), isoquinolineyl (isoquinoline-diyl), oxazole-diyl, thiazole-diyl, oxadiazole-diyl, benzothiazole-diyl, benzothiadiazole-diyl, phthalimide-diyl, thienothiazole-diyl, thiazonothiazole-diyl, thienothiazole-diyl, thienothiazono-diyl, and the structures (II-1) to (II-4) below.
[0125] [Chemical Formula 5]
[0126]
[0127] In equations (II-1) to (II-4), D1 represents -S-, -O-, or NR. 11 -, R 11 Y1 represents an alkyl group with 1 to 6 carbon atoms, Y2 represents an aromatic hydrocarbon group with 6 to 12 carbon atoms or an aromatic heterocyclic group with 3 to 12 carbon atoms, and Z1, Z2, and Z3 independently represent an aliphatic hydrocarbon group with 1 to 20 carbon atoms, an alicyclic hydrocarbon group with 3 to 20 carbon atoms, an aromatic hydrocarbon group with 6 to 20 monovalent carbon atoms, a halogen atom, a cyano group, a nitro group, and -NR, respectively.12 R 13 or -SR 12 Z1 and Z2 can bond with each other to form an aromatic ring or an aromatic heterocycle, R 12 and R 13 Each of the following groups independently represents an alkyl group having 1 to 6 carbon atoms, and J1 and J2 independently represent groups selected from -O-, -NR-, etc. 21 -(R 21 The group represents a hydrogen atom or a substituent. E represents a nonmetallic atom of group 14-16 that can bond with a hydrogen atom or a substituent. Jx represents an organic group having 2-30 carbon atoms of at least one aromatic ring selected from the group including aromatic hydrocarbon rings and aromatic heterocycles. Jy represents a hydrogen atom, an alkyl group having 1-6 carbon atoms that can have substituents, or an organic group having 2-30 carbon atoms of at least one aromatic ring selected from the group including aromatic hydrocarbon rings and aromatic heterocycles. The aromatic rings of Jx and Jy can have substituents, and Jx and Jy can bond to form a ring. D2 represents a hydrogen atom or an alkyl group having 1-6 carbon atoms that can have substituents.
[0128] In formula (II-2), when Y1 is an aromatic hydrocarbon group with 6 to 12 carbon atoms, it can be either a monocyclic or polycyclic ring. When Y1 is an aromatic heterocyclic group with 3 to 12 carbon atoms, it can be either a monocyclic or polycyclic ring.
[0129] In equation (II-2), J1 and J2 represent -NR 21 - In the case of R 21 The substituents can be described, for example, by referring to paragraphs 0035 to 0045 of Japanese Patent Application Publication No. 2008-107767, which are incorporated in the specification of this application.
[0130] In formula (II-2), when E is a nonmetallic atom of group 14 to 16 that can be bonded by a substituent, it is preferably =O, =S, =NR', or =C(R')R'. R' represents a substituent, and as a substituent, for example, it can be referred to paragraphs
[0035] to
[0045] of Japanese Patent Application Publication No. 2008-107767, preferably -NZ. A1 Z A2 (Z A1 and Z A2 Each can be represented independently by a hydrogen atom, alkyl group, or aryl group.
[0131] Specific examples of the divalent alicyclic group represented by A1 include cyclopentylene and cyclohexylene, etc., where the carbon atom can be replaced by -O-, -Si(CH3)2-, -N(Z)- (Z represents hydrogen, alkyl, cycloalkyl, aryl, cyano or halogen atom with 1 to 4 carbon atoms, -C(O)-, -S-, -C(S)-, -S(O)- and -SO2-, or groups formed by combining two or more of these groups.
[0132] In formula (MG-A), a1 represents an integer from 2 to 10. Multiple A1s can be the same or different.
[0133] In formula (MG-B), A2 and A3 are each independently a divalent group selected from the group consisting of aromatic hydrocarbon groups, heterocyclic groups, and alicyclic groups. Specific examples and preferred embodiments of A2 and A3 are the same as those of A1 in formula (MG-A), therefore their description is omitted.
[0134] In formula (MG-B), a2 represents an integer from 1 to 10. Multiple A2s can be the same or different, and multiple LA1s can be the same or different. Considering the superior effect of the present invention, a2 is more preferably 2 or more.
[0135] In formula (MG-B), LA1 is a single bond or a divalent linker. Specifically, when a2 is 1, LA1 is a divalent linker; when a2 is 2 or more, at least one of the multiple LA1s is a divalent linker.
[0136] In equation (MG-B), LA1 represents the divalent linker, which is the same as LW, so its description is omitted.
[0137] As a specific example of MG, the following structures can be cited, in which the hydrogen atoms on the aromatic hydrocarbon group, heterocyclic group and alicyclic group can be replaced by the above-mentioned substituent W.
[0138] [Chemical Formula 6]
[0139]
[0140] [Chemical Formula 7]
[0141]
[0142] [Chemical Formula 8]
[0143]
[0144] <Low molecular weight liquid crystal compounds>
[0145] When the liquid crystal compound represented by formula (LC) is a low molecular weight liquid crystal compound, the preferred cyclic structure of the mesocrystalline group MG includes cyclohexylene, cyclopentylene, phenylene, naphthylene, fluorene-diyl, pyridine-diyl, pyridazine-diyl, thiophene-diyl, oxazol-diyl, thiazole-diyl, thiophene-diyl, thiophene-thiophene-diyl, etc. The number of cyclic structures is preferably 2 to 10, and more preferably 3 to 7.
[0146] Preferred substituents W for mesocrystalline structures include halogen atoms, haloalkyl groups, cyano groups, hydroxyl groups, nitro groups, carboxyl groups, alkoxy groups with 1 to 10 carbon atoms, alkyl carbonyl groups with 1 to 10 carbon atoms, alkoxy carbonyl groups with 1 to 10 carbon atoms, alkyl carbonyloxy groups with 1 to 10 carbon atoms, amino groups, alkyl amino groups with 1 to 10 carbon atoms, alkyl amino carbonyl groups, groups in the above formula (W1) where LW is a single bond, SPW is a divalent spacer group, and Q is a crosslinking group represented by (P1) to (P30) above. As crosslinking groups, vinyl, butadiene, (meth)acrylic acid, (meth)acrylamide, vinyl acetate, fumarate, styrene, vinylpyrrolidone, maleic anhydride, maleimide, vinyl ether, epoxy, or oxetane.
[0147] The preferred methods for the divalent spacers S1 and S2 are the same as those for the SPW described above, so their description is omitted.
[0148] When using a low-molecular-weight liquid crystal compound exhibiting smectic properties, the number of carbon atoms in the spacer group (which is the number of atoms when the carbon is replaced by "SP-C") is preferably 6 or more, and more preferably 8 or more.
[0149] When the liquid crystal compound represented by formula (LC) is a low-molecular-weight liquid crystal compound, multiple low-molecular-weight liquid crystal compounds can be used simultaneously, preferably 2 to 6 types, and more preferably 2 to 4 types. By using low-molecular-weight liquid crystal compounds simultaneously, the solubility can be improved or the phase transition temperature of the liquid crystal composition can be adjusted.
[0150] Specific examples of low-molecular-weight liquid crystal compounds include compounds represented by the formulas (LC-1) to (LC-77), but low-molecular-weight liquid crystal compounds are not limited to these.
[0151] [Chemical Formula 9]
[0152]
[0153] [Chemical Formula 10]
[0154]
[0155] <Molecular Liquid Crystal Compounds>
[0156] The polymeric liquid crystal compound is preferably a homopolymer or copolymer containing repeating units described later, and can be any polymer such as random polymer, block polymer, graft polymer, star polymer, etc.
[0157] (Repeated unit (1))
[0158] The polymeric liquid crystal compound preferably contains a repeating unit represented by formula (1) (hereinafter also referred to as "repeating unit (1)").
[0159] [Chemical Formula 11]
[0160]
[0161] In formula (1), PC1 represents the main chain of the repeating unit, L1 represents a single bond or a divalent linker, SP1 represents a spacer, MG1 represents the mesocrystalline group MG in the above formula (LC), and T1 represents a terminal group.
[0162] As the main chain of the repeating unit represented by PC1, for example, groups represented by formulas (P1-A) to (P1-D) can be cited. Among them, from the viewpoint of the diversity of monomers that can be used as raw materials and ease of handling, groups represented by the following formula (P1-A) are preferred.
[0163] [Chemical Formula 12]
[0164]
[0165] In equations (P1-A) to (P1-D), "*" indicates the bonding position with L1 in equation (1). In equations (P1-A) to (P1-D), R... 11 R 12 R 13 R 14 Each of the above-mentioned alkyl groups independently represents a hydrogen atom, a halogen atom, a cyano group, or an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms. The alkyl group can be a straight-chain or branched alkyl group, or an alkyl group having a cyclic structure (cycloalkyl). Furthermore, the number of carbon atoms in the alkyl group is preferably 1 to 5.
[0166] The group represented by formula (P1-A) is preferably a unit of a partial structure of poly(meth)acrylate obtained by polymerization of (meth)acrylate.
[0167] The group represented by formula (P1-B) is preferably an ethylene glycol unit formed by ring-opening polymerization of the epoxy group of a compound having an epoxy group.
[0168] The group represented by formula (P1-C) is preferably a propylene glycol unit formed by ring-opening polymerization of an oxetane compound having an oxetane.
[0169] The group represented by formula (P1-D) is preferably a siloxane unit of a polysiloxane obtained by polycondensation of a compound having at least one of alkoxysilyl and silanol groups. Here, as a compound having at least one of alkoxysilyl and silanol groups, an example is a compound having the formula SiR 14 (OR 15 Compounds containing a group represented by )2-. In the formula, R 14 R in (P1-D) 14 The meanings are the same, multiple R 15 Alkyl groups, each independently representing 1 to 10 hydrogen or carbon atoms.
[0170] The divalent linker represented by L1 is the same divalent linker as LW in the above formula (W1). As a preferred embodiment, -C(O)O-, -OC(O)-, -O-, -S-, and -C(O)NR can be cited. 16 -、-NR 16 C(O)-, -S(O)2- and -NR 16 R 17 - etc. In the formula, R 16 and R 1 7 represents a hydrogen atom and an alkyl group having 1 to 6 carbon atoms, which may have substituents (e.g., substituent W mentioned above). In a specific example of a divalent linker, the left-hand bond is bonded to PC1, and the right-hand bond is bonded to SP1.
[0171] When PC1 is a group represented by formula (P1-A), L1 is preferably -C(O)O- or -C(O)NR. 16 - indicates a functional group.
[0172] When PC1 is a group represented by formulas (P1-B) to (P1-D), L1 is preferably a single bond.
[0173] The spacer group represented by SP1 is the same group as S1 and S2 in the above formula (LC). From the viewpoint of orientation, it is preferable to include a group with at least one structure selected from the group consisting of ethylene oxide structure, propylene oxide structure, polysiloxane structure and fluorinated alkylene structure, or a straight-chain or branched alkylene group having 2 to 20 carbon atoms. The alkylene group may include -O-, -S-, -O-CO-, -CO-O-, -O-CO-O-, -O-CNR- (R represents an alkyl group having 1 to 10 carbon atoms), or -S(O)2-.
[0174] Considering reasons such as ease of liquid crystal properties or availability of raw materials, the spacer group represented by SP1 is more preferably a group comprising at least one structure selected from the group consisting of ethylene oxide structure, propylene oxide structure, polysiloxane structure and fluorinated alkylene structure.
[0175] Here, the oxyethylene structure represented by SP1 is preferably composed of *-(CH2-CH2O). n1 -* indicates a group. In the formula, n1 represents an integer from 1 to 20, and * indicates the bonding position with L1 or MG1. For the sake of better performance of the present invention, n1 is preferably an integer from 2 to 10, more preferably an integer from 2 to 6, and most preferably 2 to 4.
[0176] Furthermore, the oxypropylidene structure represented by SP1 is preferably composed of *-(CH(CH3)-CH2O). n2 -* indicates a group. In the formula, n2 represents an integer from 1 to 3, and * indicates the bonding position with L1 or MG1.
[0177] Furthermore, the polysiloxane structure represented by SP1 is preferably represented by a group consisting of *-(Si(CH3)2-O)n3-*. In this formula, n3 represents an integer from 6 to 10, and * represents the bonding position with L1 or MG1.
[0178] Furthermore, the fluorinated alkylene structure represented by SP1 is preferably composed of *-(CF2-CF2). n4 -* indicates a group. In the formula, n4 represents an integer from 6 to 10, and * indicates the bonding position with L1 or MG1.
[0179] Examples of terminal groups represented by T1 include hydrogen atoms, halogen atoms, cyano groups, nitro groups, hydroxyl groups, -SH groups, carboxyl groups, borate groups, -SO3H groups, -PO3H2 groups, and -NR groups. 11 R 12 (R 11 and R 12 These groups can be independently represented by alkyl, cycloalkyl, or aryl groups with 1 to 10 carbon atoms (either substituted or unsubstituted), alkyl groups with 1 to 10 carbon atoms, alkoxy groups with 1 to 10 carbon atoms, alkylthio groups with 1 to 10 carbon atoms, alkoxycarbonyloxy groups with 1 to 10 carbon atoms, acyloxy groups with 1 to 10 carbon atoms, amide groups with 1 to 10 carbon atoms, alkoxycarbonyl groups with 1 to 10 carbon atoms, alkoxycarbonylamino groups with 1 to 10 carbon atoms, sulfonylamino groups with 1 to 10 carbon atoms, aminosulfonyl groups with 1 to 10 carbon atoms, carbamoyl groups with 1 to 10 carbon atoms, sulfinyl groups with 1 to 10 carbon atoms, ureido groups with 1 to 10 carbon atoms, and groups containing crosslinking groups.
[0180] Examples of groups containing crosslinking groups include -L-CL. L represents a single bond or a linker. Specific examples of linkers are the same as LW and SPW described above. CL represents a crosslinking group, and examples include groups represented by Q1 or Q2 described above, preferably groups represented by formulas (P1) to (P30) described above. Furthermore, T1 can also be a group formed by combining two or more of these groups.
[0181] For the sake of superior effects of the present invention, T1 is preferably an alkoxy group having 1 to 10 carbon atoms, more preferably an alkoxy group having 1 to 5 carbon atoms, and even more preferably a methoxy group. These terminal groups can be further replaced by these groups or polymerizable groups described in Japanese Patent Application Publication No. 2010-244038.
[0182] For the sake of superior performance of the present invention, the number of atoms in the main chain of T1 is preferably 1 to 20, more preferably 1 to 15, even more preferably 1 to 10, and particularly preferably 1 to 7. When the number of atoms in the main chain of T1 is 20 or less, the orientation degree of the light-absorbing anisotropic layer is further improved. Here, "main chain" in T1 refers to the longest molecular chain bonded to M1, and hydrogen atoms are not included in the number of atoms in the main chain of T1. For example, when T1 is n-butyl, the number of atoms in the main chain is 4; when T1 is sec-butyl, the number of atoms in the main chain is 3.
[0183] The content of the repeating unit (1) is preferably 40 to 100% by mass, more preferably 50 to 95% by mass, relative to all repeating units (100% by mass) in the polymeric liquid crystal compound. If the content of the repeating unit (1) is 40% by mass or more, a light absorption anisotropy layer with good orientation can be obtained. Furthermore, if the content of the repeating unit (1) is 100% by mass or less, a light absorption anisotropy layer with good orientation can be obtained.
[0184] The polymeric liquid crystal compound may contain only one repeating unit (1) or two or more repeating units (1). When it contains two or more repeating units (1), the content of the repeating unit (1) refers to the total content of the repeating units (1).
[0185] (logP value)
[0186] In equation (1), the difference (|logP1-logP2|) between the logP values (hereinafter also referred to as "logP1") of PC1, L1 and SP1 and the logP value (hereinafter also referred to as "logP2") of MG1 is 4 or more. From the viewpoint of further improving the orientation degree of the light absorption anisotropy layer, it is preferably 4.25 or more, and more preferably 4.5 or more.
[0187] Furthermore, from the viewpoint of adjusting the liquid crystal phase transition temperature and the suitability of synthesis, the upper limit of the above-mentioned difference is preferably 15 or less, more preferably 12 or less, and even more preferably 10 or less.
[0188] Here, the logP value is an indicator of the hydrophilicity and hydrophobicity of a chemical structure, sometimes referred to as the hydrophilicity-hydrophobicity parameter. The logP value can be calculated using software such as ChemBioDraw Ultra or HSPiP (Ver. 4.1.07). It can also be determined experimentally using methods such as those outlined in the OECD Guidelines for the Testing of Chemica, Section 1, Test No. 117. Unless otherwise specified, in this invention, the logP value is calculated using the structural formula of the compound entered into HSPiP (Ver. 4.1.07).
[0189] As mentioned above, logP1 refers to the logP values of PC1, L1, and SP1. The "logP values of PC1, L1, and SP1" refers to the logP value of the structure in which PC1, L1, and SP1 are set as a single unit, and is not the sum of the individual logP values of PC1, L1, and SP1. Specifically, logP1 is calculated by inputting a series of structural formulas of PC1 to SP1 in equation (1) into the software mentioned above.
[0190] When calculating logP1, in the series of structural formulas PC1 to SP1, the part about the group represented by PC1 can use the structure of the group represented by PC1 itself (e.g., the above formulas (P1-A) to (P1-D) etc.), or the structure of the group that can become PC1 after the monomer used to obtain the repeating unit represented by formula (1) is polymerized.
[0191] Here, specific examples of the latter (which can be the group that makes up PC1) are as follows. In the case where PC1 is obtained by the polymerization of (meth)acrylate, it is formed by CH2=C(R) 1 )- represents the group (R) 1 (This represents a hydrogen atom or a methyl group.) Furthermore, when PC1 is obtained by polymerization of ethylene glycol, it is ethylene glycol; when PC1 is obtained by polymerization of propylene glycol, it is propylene glycol. Also, when PC1 is obtained by condensation polymerization of silanol, it is silanol (from the formula Si(R...). 2 Compounds represented by )3(OH). Multiple R 2 Each R represents a hydrogen atom or an alkyl group independently. Multiple R groups are used to represent hydrogen atoms or alkyl groups. 2 At least one of them represents an alkyl group.
[0192] If the difference between logP1 and logP2 is 4 or more, then logP1 can be lower or higher than logP2.
[0193] Here, the logP value of a typical mesocrystalline group (logP2 mentioned above) tends to be in the range of 4 to 6. In this case, when logP1 is lower than logP2, the value of logP1 is preferably 1 or less, more preferably 0 or less. On the other hand, when logP1 is higher than logP2, the value of logP1 is preferably 8 or more, more preferably 9 or more.
[0194] When PC1 in formula (1) is obtained by polymerization of (meth)acrylate and logP1 is lower than logP2, the logP value of SP1 in formula (1) is preferably 0.7 or less, more preferably 0.5 or less. On the other hand, when PC1 in formula (1) is obtained by polymerization of (meth)acrylate and logP1 is higher than logP2, the logP value of SP1 in formula (1) is preferably 3.7 or more, more preferably 4.2 or more.
[0195] Furthermore, examples of structures with a logP value of 1 or less include the oxyethylene structure and the oxypropylene structure. Examples of structures with a logP value of 6 or more include the polysiloxane structure and the fluorinated alkylene structure.
[0196] (Repeated units (21) and (22))
[0197] From the viewpoint of improving the degree of orientation, the polymeric liquid crystal compound preferably contains repeating units with electron-donating and / or electron-withdrawing properties at its ends. More specifically, it is more preferable to contain repeating units (21) having mesocrystalline groups and electron-withdrawing groups with σp values greater than 0 at their ends, and repeating units (22) having mesocrystalline groups and groups with σp values less than 0 at their ends. Thus, when the polymeric liquid crystal compound contains repeating units (21) and repeating units (22), the degree of orientation of the light-absorbing anisotropic layer formed therefrom is improved compared to the case where only one of the repeating units (21) or (22) is contained. Although the detailed reasons are not yet clear, they are roughly speculated to be as follows.
[0198] That is, it is speculated that through the interaction between molecules by the opposite dipole moments generated in the repeating units (21) and (22), the interaction of the mesocrystalline groups in the short axis direction becomes stronger, the orientation of the liquid crystal becomes more uniform, and as a result, the degree of order of the liquid crystal is considered to be higher. Thus, it is speculated that the orientation of the dichroic material also becomes better, and therefore the degree of orientation of the formed light absorption anisotropic layer is higher.
[0199] In addition, the repeating units (21) and (22) mentioned above can also be repeating units represented by the above formula (1).
[0200] The repeating unit (21) has a mesocrystalline group and an electron-withdrawing group with a σp value greater than 0 at the end of the mesocrystalline group.
[0201] The electron-withdrawing groups mentioned above are those located at the end of the mesocrystalline group and have a σp value greater than 0. Examples of electron-withdrawing groups (groups with a σp value greater than 0) include the group represented by EWG in formula (LCP-21) described later, and specific examples are similar.
[0202] The σp value of the aforementioned electron-withdrawing groups is greater than 0. From the perspective of increasing the orientation degree of the light-absorbing anisotropic layer, it is preferably 0.3 or more, and more preferably 0.4 or more. From the perspective of excellent orientation uniformity, the upper limit of the σp value of the aforementioned electron-withdrawing groups is preferably 1.2 or less, and more preferably 1.0 or less.
[0203] The σp value refers to the Hammett substituent constant σp (also simply called "σp value"), which numerically represents the effect of the substituent at the acid dissociation equilibrium constant of benzoic acid. It is a parameter indicating the strength of the electron-withdrawing and electron-donating properties of the substituent. The Hammett substituent constant σp value in this specification refers to the substituent constant σ when the substituent is located at the para position of benzoic acid.
[0204] The Hammett substituent constant σp values for each group in this specification are those described in the literature "Hansch et al., Chemical Reviews, 1991, Vol. 91, No. 2, 165-195". Furthermore, for groups for which the Hammett substituent constant σp value is not specified in the aforementioned literature, the Hammett substituent constant σp value can be calculated using the software "ACD / ChemSketch (ACD / Labs 8.00 Release Product Version: 8.08)" based on the difference between the pKa of benzoic acid and the pKa of a benzoic acid derivative with a substituent at the para position.
[0205] The repeating unit (21) is not particularly limited as long as it has a mesocrystalline group in the side chain and an electron-withdrawing group with a σp value greater than 0 at the end of the mesocrystalline group. From the viewpoint that the orientation degree of the light-absorbing anisotropic layer becomes higher, the repeating unit represented by the following formula (LCP-21) is preferred.
[0206] [Chemical Formula 13]
[0207]
[0208] In formula (LCP-21), PC21 represents the main chain of repeating units, more specifically, the same structure as PC1 in formula (1) above; L21 represents a single bond or a divalent linker, more specifically, the same structure as L1 in formula (1) above; SP21A and SP21B represent single bonds or spacer groups, respectively, with specific examples of spacer groups representing the same structure as SP1 in formula (1) above; MG21 represents a mesocrystalline structure, more specifically, the mesocrystalline group MG in formula (LC) above; and EWG represents an electron-withdrawing group with a σp value greater than 0.
[0209] The spacer groups represented by SP21A and SP21B represent groups identical to those in formulas S1 and S2 above, and preferably include groups with at least one structure selected from the group consisting of ethylene oxide, propylene oxide, polysiloxane, and fluorinated alkylene structures, or straight-chain or branched alkylene groups having 2 to 20 carbon atoms. The aforementioned alkylene groups may include -O-, -O-CO-, -CO-O-, or -O-CO-O-.
[0210] For reasons such as ease of liquid crystal properties or availability of raw materials, the spacer group represented by SP1 preferably includes at least one structure selected from the group consisting of ethylene oxide structure, propylene oxide structure, polysiloxane structure and fluorinated alkylene structure.
[0211] SP21B is preferably a single bond or a straight-chain or branched alkylene group having 2 to 20 carbon atoms. The alkylene group may contain -O-, -O-CO-, -CO-O-, or -O-CO-O-.
[0212] From the perspective of increasing the orientation degree of the light-absorbing anisotropic layer, the spacer group represented by SP21B is preferably a single bond. In other words, the repeating unit 21 preferably has a structure in which the electron-withdrawing group EWG, which is an electron-withdrawing group in formula (LCP-21), is directly bonded to the mesocrystalline group MG21, which is a mesocrystalline group in formula (LCP-21). Thus, it is speculated that if the electron-withdrawing group and the mesocrystalline group are directly bonded, the intermolecular interactions generated by the moderate dipole moment in the polymeric liquid crystal compound will work more effectively, the orientation of the liquid crystal will become more uniform, and as a result, the degree of order of the liquid crystal is considered to be higher, and the degree of orientation is also higher.
[0213] EWG indicates an electron-withdrawing group with a σp value greater than 0. Examples of electron-withdrawing groups with a σp value greater than 0 include ester groups (specifically, those derived from *-C(O)OR). E (represented by groups), (meth)acryloyl, (meth)acryloyloxy, carboxyl, cyano, nitro, sulfonyl, -S(O)(O)-OR E -S(O)(O)-R E -OS(O)(O)-R EAcyl group (specifically, composed of *-C(O)R) E The group represented), acyloxy group (specifically, represented by *-OC(O)R) E (represented by groups), isocyanate group (-N=C(O)), *-C(O)N(R) F 2. Halogen atoms and alkyl groups substituted by these groups (preferably with 1 to 20 carbon atoms). In the above groups, * indicates the bonding position with SP21B. R E R represents an alkyl group having 1 to 20 carbon atoms (preferably 1 to 4 carbon atoms, more preferably 1 to 2 carbon atoms). F Alkyl groups, each independently representing a hydrogen atom or a carbon atom number of 1 to 20 (preferably 1 to 4 carbon atoms, more preferably 1 to 2 carbon atoms).
[0214] In view of further enhancing the effects of the present invention, among the above-mentioned groups, EWG is preferably composed of *-C(O)OR E The indicated groups are (meth)acryloyloxy or cyano, and nitro.
[0215] From the perspective of maintaining a high degree of orientation of the light absorption anisotropy layer and enabling uniform orientation of the polymer liquid crystal compound and the dichroic material, the content of the repeating unit (21) is preferably 60% by mass or less, more preferably 50% by mass or less, and especially preferably 45% by mass or less, relative to all repeating units (100% by mass) of the polymer liquid crystal compound.
[0216] From the viewpoint of further maximizing the effects of the present invention, the lower limit of the content of the repeating unit (21) is preferably 1% by mass or more, more preferably 3% by mass or more, relative to all repeating units (100% by mass) of the polymeric liquid crystal compound.
[0217] In this invention, the content of each repeating unit contained in the polymeric liquid crystal compound is calculated based on the amount (mass) of each monomer added to obtain each repeating unit.
[0218] The polymeric liquid crystal compound may contain only one repeating unit (21) or two or more repeating units. If the polymeric liquid crystal compound contains two or more repeating units (21), it has advantages such as improved solubility of the polymeric liquid crystal compound in solvents and easier adjustment of the liquid crystal phase transition temperature. When it contains two or more repeating units (21), it is preferable that their total amount is within the above-mentioned range.
[0219] When two or more repeating units (21) are included, repeating units (21) that do not contain crosslinking groups in the EWG and repeating units (21) that contain polymerizable groups in the EWG can be used simultaneously. As a result, the curability of the light-absorbing anisotropic layer is further improved. In addition, as crosslinking groups, vinyl, butadiene, (meth)acrylate, (meth)acrylamide, vinyl acetate, fumarate, styrene, vinylpyrrolidone, maleic anhydride, maleimide, vinyl ether, epoxy, and oxetyl are preferred.
[0220] At this point, considering the balance between the curability and orientation of the light-absorbing anisotropic layer, the content of repeating units (21) containing polymeric groups in the EWG is preferably 1 to 30% by mass relative to all repeating units (100% by mass) of the polymeric liquid crystal compound.
[0221] The following is an example of a repeating unit (21), but the repeating unit (21) is not limited to the following repeating units.
[0222] [Chemical Formula 14]
[0223]
[0224] Regarding the repeating unit (21) and repeating unit (22), the inventors conducted in-depth research on the composition (content ratio) and the electron-donating and electron-withdrawing properties of the terminal groups. They found that when the electron-withdrawing properties of the electron-withdrawing groups of the repeating unit (21) are strong (i.e., the σp value is large), if the content ratio of the repeating unit (21) is reduced, the orientation degree of the light-absorbing anisotropic layer becomes higher. When the electron-withdrawing properties of the electron-withdrawing groups of the repeating unit (21) are weak (i.e., the σp value is close to 0), if the content ratio of the repeating unit (21) is increased, the orientation degree of the light-absorbing anisotropic layer becomes higher.
[0225] While the detailed reasons are not yet clear, they are roughly speculated as follows: It is speculated that through the intermolecular interactions generated by a moderate dipole moment in the polymeric liquid crystal compound, the orientation of the liquid crystal becomes more uniform. As a result, the degree of order of the liquid crystal is considered to be higher, and the orientation degree of the light absorption anisotropic layer becomes higher.
[0226] Specifically, the product of the σp value of the electron-withdrawing group (EWG in formula (LCP-21)) in the repeating unit (21) and the content ratio (by mass) of the repeating unit (21) in the polymeric liquid crystal compound is preferably 0.020 to 0.150, more preferably 0.050 to 0.130, and particularly preferably 0.055 to 0.125. If the product is within the above range, the orientation degree of the light-absorbing anisotropic layer becomes higher.
[0227] The repeating unit (22) has a mesocrystalline group and a group with a σp value of 0 or less at the end of the mesocrystalline group. By having the repeating unit (22) in the polymeric liquid crystal compound, the polymeric liquid crystal compound and the dichroic substance can be uniformly oriented.
[0228] Mesocrystalline groups are groups that represent the main framework of liquid crystal molecules that contribute to the formation of liquid crystals. Details are explained in MG of formula (LCP-22) described later, and specific examples are the same.
[0229] The aforementioned groups are those located at the end of a mesocrystalline group and have a σp value of 0 or less. Examples of such groups (groups with a σp value of 0 or less) include hydrogen atoms with a σp value of 0 and groups represented by T22 in the following formula (LCP-22) with a σp value less than 0 (electron-donating groups). Specific examples of groups with a σp value less than 0 (electron-donating groups) are the same as T22 in the following formula (LCP-22).
[0230] The σp value of the above-mentioned groups is 0 or less. From the perspective of better orientation uniformity, it is preferable to be less than 0, more preferably less than -0.1, and especially preferably less than -0.2. The lower limit of the σp value of the above-mentioned groups is preferably more than -0.9, and more preferably more than -0.7.
[0231] The repeating unit (22) is not particularly limited as long as it has a mesocrystalline group in the side chain and a group with a σp value of 0 or less at the end of the mesocrystalline group. From the viewpoint of making the orientation uniformity of the liquid crystal higher, the repeating unit represented by the following formula (PCP-22) is preferred and does not conform to the repeating unit represented by the above formula (LCP-21).
[0232] [Chemical Formula 15]
[0233]
[0234] In formula (LCP-22), PC22 represents the main chain of the repeating unit, more specifically, the same structure as PC1 in formula (1) above; L22 represents a single bond or divalent linker, more specifically, the same structure as L1 in formula (1) above; SP22 represents a spacer group, more specifically, the same structure as SP1 in formula (1) above; MG22 represents a mesocrystalline structure, more specifically, the same structure as the mesocrystalline group MG in formula (LC) above; and T22 represents an electron-donating group with a Hammett substituent constant σp value less than 0.
[0235] T22 indicates an electron-donating group with a σp value less than 0. Examples of electron-donating groups with a σp value less than 0 include hydroxyl groups, alkyl groups with 1 to 10 carbon atoms, alkoxy groups with 1 to 10 carbon atoms, and alkylamino groups with 1 to 10 carbon atoms.
[0236] By using T22 with a main chain of 20 or fewer atoms, the orientation degree of the anisotropic layer for light absorption is further improved. Here, "main chain" in T22 refers to the longest molecular chain bonded to MG22, excluding hydrogen atoms from the main chain atomic count. For example, when T22 is n-butyl, the main chain has 4 atoms, and when T22 is sec-butyl, the main chain has 3 atoms.
[0237] The following is an example of a repeating unit (22), but the repeating unit (22) is not limited to the following repeating units.
[0238] [Chemical Formula 16]
[0239]
[0240] It is preferred that the repeating units (21) and (22) share a portion of the structure. It is speculated that the more similar the structures of the repeating units are to each other, the more uniformly the liquid crystals are arranged. As a result, the orientation degree of the light-absorbing anisotropic layer becomes higher.
[0241] Specifically, considering that the orientation degree of the light absorption anisotropy layer becomes higher, it is preferable that at least one of the following is satisfied: SP21A of formula (LCP-21) and SP22 of formula (LCP-22) are the same structure; MG21 of formula (LCP-21) and MG22 of formula (LCP-22) are the same structure; and L21 of formula (LCP-21) and L22 of formula (LCP-22) are the same structure. More preferably, two or more are satisfied, and especially preferably all of them are satisfied.
[0242] From the perspective of excellent orientation uniformity, the content of repeating unit (22) is preferably 50% by mass or more, more preferably 55% by mass or more, and especially preferably 60% by mass or more, relative to all repeating units (100% by mass) of the polymeric liquid crystal compound.
[0243] From the perspective of improving orientation, the upper limit of the content of repeating unit (22) is preferably 99% by mass or less, more preferably 97% by mass or less, relative to all repeating units (100% by mass) of the polymeric liquid crystal compound.
[0244] The polymeric liquid crystal compound may contain a single repeating unit (22) or two or more repeating units. If the polymeric liquid crystal compound contains two or more repeating units (22), it has advantages such as improved solubility of the polymeric liquid crystal compound in solvents and easier adjustment of the liquid crystal phase transition temperature. In the case of containing two or more repeating units (22), it is preferable that their total amount is within the above-mentioned range.
[0245] (Repeated unit (3))
[0246] From the viewpoint of improving solubility in common solvents, polymeric liquid crystal compounds can contain repeating units (3) that do not contain mesomorphic crystals. In particular, in order to suppress the decrease in orientation degree and improve solubility, the repeating unit (3) that does not contain mesomorphic crystals is preferably a repeating unit with a molecular weight of 280 or less. Thus, the reason for suppressing the decrease in orientation degree and improving solubility by containing repeating units with a molecular weight of 280 or less that do not contain mesomorphic crystals is speculated as follows.
[0247] That is, it is believed that by including non-mesocrystalline repeating units (3) in the molecular chain of the polymeric liquid crystal compound, the solvent can easily enter the polymeric liquid crystal compound, thus increasing the solubility. However, the non-mesocrystalline repeating units (3) will cause the orientation degree to decrease. However, it is speculated that because the molecular weight of the repeating units is small, the orientation of the repeating units (1), repeating units (21) or repeating units (22) containing mesocrystalline groups is not easily disordered, which can suppress the decrease in orientation degree.
[0248] The repeating unit (3) is preferably a repeating unit with a molecular weight of 280 or less.
[0249] The molecular weight of the repeating unit (3) does not refer to the molecular weight of the monomer used to obtain the repeating unit (3), but rather to the molecular weight of the repeating unit (3) in the state of being combined into a polymeric liquid crystal compound through the polymerization of the monomer.
[0250] The molecular weight of the repeating unit (3) is 280 or less, preferably 180 or less, and more preferably 100 or less. The lower limit of the molecular weight of the repeating unit (3) is usually 40 or more, and more preferably 50 or more. If the molecular weight of the repeating unit (3) is 280 or less, a light-absorbing anisotropic layer with excellent solubility and high orientation of the polymer liquid crystal compound can be obtained.
[0251] On the other hand, if the molecular weight of the repeating unit (3) exceeds 280, it leads to disordered liquid crystal orientation of the repeating unit (1), repeating unit (21), or repeating unit (22) and sometimes reduces the degree of orientation. Furthermore, since the solvent has difficulty entering the liquid crystal compound, the solubility of the liquid crystal compound sometimes decreases.
[0252] As specific examples of repeating unit (3), there are repeating units that do not contain crosslinking groups (e.g., olefinic unsaturated groups) (hereinafter also referred to as "repeating unit (3-1)") and repeating units that contain crosslinking groups (hereinafter also referred to as "repeating unit (3-2)").
[0253] • Repeating unit (3-1)
[0254] Specific examples of monomers used in the polymerization of repeating unit (3-1) include acrylic acid [72.1], α-alkyl acrylic acids (e.g., methacrylic acid [86.1], itaconic acid [130.1]), esters and amides derived from them (e.g., N-isopropylacrylamide [113.2], N-n-butylacrylamide [127.2], N-tert-butylacrylamide [127.2], N,N-dimethylacrylamide [99.1], N-methylmethacrylamide [99.1], acrylamide [71.1], methacrylamide [85.1], diacetone acrylamide [169.2], acryloylmorpholine [141.2], N-hydroxymethylacrylamide [101.1], N-hydroxy... Methylmethacrylamide [115.1], methyl acrylate [86.0], ethyl acrylate [100.1], hydroxyethyl acrylate [116.1], n-propyl acrylate [114.1], isopropyl acrylate [114.2], 2-hydroxypropyl acrylate [130.1], 2-methyl-2-nitropropyl acrylate [173.2], n-butyl acrylate [128.2], isobutyl acrylate [128.2], tert-butyl acrylate [128.2], tert-amyl acrylate [142.2], 2-methoxyethyl acrylate [130.1], 2-ethoxyethyl acrylate [144.2], 2-ethoxyethoxyethyl acrylate [188.2], 2,2,2-trifluoroethyl acrylate [154.1], 2,2-Dimethylbutyl acrylate [156.2], 3-Methoxybutyl acrylate [158.2], Ethyl carbitol acrylate [188.2], Phenoxyethyl acrylate [192.2], n-Amyl acrylate [142.2], n-Hexyl acrylate [156.2], Cyclohexyl acrylate [154.2], Cyclopentyl acrylate [140.2], Benzyl acrylate [162.2], n-Octyl acrylate [184.3], 2-Ethylhexyl acrylate [184.3], 4-Methyl-2-propylpentyl acrylate [198.3], Methyl methacrylate [100.1], 2,2,2-Trifluoroethyl methacrylate [168.1], Hydroxyethyl methacrylate [130.1], 2-hydroxypropyl methacrylate [144.2], n-butyl methacrylate [142.2], isobutyl methacrylate [142.2], sec-butyl methacrylate [142.2], n-octyl methacrylate [198.3], 2-ethylhexyl methacrylate [198.3], 2-methoxyethyl methacrylate [144.2], 2-ethoxyethyl methacrylate [158.2], benzyl methacrylate [176.2], 2-norbornyl methyl methacrylate [194.3], 5-norbornen-2-yl methyl methacrylate [194.3], dimethylaminoethyl methacrylate [157.2]), vinyl esters (e.g., vinyl acetate [86.1) Esters derived from maleic acid or fumaric acid (e.g., dimethyl maleate [144.1], diethyl fumarate [172.2]), maleimides (e.g., N-phenylmaleimide [173.2]), maleic acid [116.1], fumaric acid [116.1], p-styrenesulfonic acid [184.1], acrylonitrile [53.1], methacrylonitrile [67.1], dienes (e.g., butadiene [54.1], cyclopentadiene [66.1], isoprene [68.1]), aromatic vinyl compounds (e.g., styrene [104.2], p-chlorostyrene [138.6], tert-butylstyrene [160.3], α-methylstyrene [118.2]), N-vinylpyrrolidone [111.1], N-ethyl Alkenyl oxazolidinones [113.1], N-vinylsuccinimide [125.1], N-vinylformamide [71.1], N-vinyl-N-methylformamide [85.1], N-vinylacetamide [85.1], N-vinyl-N-methylacetamide [99.1], 1-vinylimidazolium [94.1], 4-vinylpyridine [105.2], vinyl sulfonic acid [108.1], sodium vinyl sulfonate [130.2], sodium allyl sulfonate [144.1], sodium methyl allyl sulfonate [158.2], vinylidene chloride [96.9], vinyl alkyl ethers (e.g., methyl vinyl ether [58.1]), ethylene [28.0], propylene [42.1], 1-butene [56.1], and isobutene [56.1]. Additionally, the values in brackets [] refer to the molecular weight of the monomer.
[0255] The above monomers can be used alone or in combination with two or more.
[0256] Among the monomers mentioned above, acrylic acid, α-alkyl acrylic acids, esters and amides derived from them, acrylonitrile, methacrylonitrile, and aromatic vinyl compounds are preferred.
[0257] Other monomers than those mentioned above can be used, for example, compounds described in Research Disclosure No. 1955 (July 1980).
[0258] The following examples of repeating units (3-1) and their molecular weights are shown, but the present invention is not limited to these specific examples.
[0259] [Chemical Formula 17]
[0260]
[0261] • Repeating unit (3-2)
[0262] In the repeating unit (3-2), specific examples of crosslinking groups can be the groups represented by P1 to P30 above, more preferably vinyl, butadiene, (meth)acrylic acid, (meth)acrylamide, vinyl acetate, fumarate, styrene, vinylpyrrolidone, maleic anhydride, maleimide, vinyl ether, epoxy, and oxetyl.
[0263] From the perspective of ease of aggregation, the repeating unit (3-2) is preferably a repeating unit represented by the following formula (3).
[0264] [Chemical Formula 18]
[0265]
[0266] In the above formula (3), PC32 represents the main chain of the repeating unit, more specifically, the same structure as PC1 in the above formula (1), L32 represents a single bond or a divalent linker, more specifically, the same structure as L1 in the above formula (1), and P32 represents the crosslinking group represented by the above formulas (P1) to (P30).
[0267] The following examples of repeating units (3-2) and their weight-average molecular weights (Mw) are shown, but the present invention is not limited to these specific examples.
[0268] [Chemical Formula 19]
[0269]
[0270] The content of repeating unit (3) is less than 14% by mass relative to all repeating units (100% by mass) of the polymeric liquid crystal compound, preferably 7% by mass or less, more preferably 5% by mass or less. The lower limit of the content of repeating unit (3) relative to all repeating units (100% by mass) of the polymeric liquid crystal compound is preferably 2% by mass or more, more preferably 3% by mass or more. If the content of repeating unit (3) is less than 14% by mass, the orientation degree of the light-absorbing anisotropic layer is further improved. If the content of repeating unit (3) is 2% by mass or more, the solubility of the polymeric liquid crystal compound is further improved.
[0271] The polymeric liquid crystal compound may contain only one repeating unit (3) or two or more. When two or more repeating units (3) are contained, it is preferable that their total amount is within the above range.
[0272] (Repeated unit (4))
[0273] From the perspective of improving adhesion or planar uniformity, polymeric liquid crystal compounds can contain repeating units (4) with a flexible structure having a molecular chain length (SP4 of formula (4) described later). The reason for this is as follows.
[0274] That is, by incorporating a flexible structure with such long molecular chains, it is easy to generate entanglement between the molecular chains constituting the polymeric liquid crystal compound, which can suppress the cohesive destruction of the light absorption anisotropic layer (specifically, the destruction of the light absorption anisotropic layer itself). As a result, it is presumed that the adhesion between the light absorption anisotropic layer and the substrate layer (e.g., a substrate or alignment film) is improved. Furthermore, it is believed that the decrease in planar uniformity is due to the low compatibility between the dichroic material and the polymeric liquid crystal compound. That is, it is believed that if the compatibility between the dichroic material and the polymeric liquid crystal compound is insufficient, planar defects (alignment defects) with the precipitated dichroic material as the core will occur. In contrast, it is presumed that by incorporating a flexible structure with long molecular chains in the polymeric liquid crystal compound, the precipitation of the dichroic material is suppressed, thereby obtaining a light absorption anisotropic layer with excellent planar uniformity. Here, excellent planar uniformity means fewer alignment defects caused by the liquid crystal composition containing the polymeric liquid crystal compound being repelled on the substrate layer (e.g., a substrate or alignment film).
[0275] The repeating unit (4) mentioned above is a repeating unit represented by the following formula (4).
[0276] [Chemical Formula 20]
[0277]
[0278] In the above formula (4), PC4 represents the main chain of the repeating unit, more specifically, the same structure as PC1 in the above formula (1), L4 represents a single bond or a divalent linker, more specifically, the same structure as L1 in the above formula (1) (preferably a single bond), SP4 represents an alkylene group with 10 or more atoms in the main chain, and T4 represents a terminal group, more specifically, the same structure as T1 in the above formula (1).
[0279] The specific example and preferred method of PC4 are the same as PC1 in equation (1), so its description is omitted.
[0280] From the perspective of further maximizing the effects of the present invention, L4 is preferably a single bond.
[0281] In formula (4), SP4 represents an alkylene group with 10 or more atoms in the main chain. One or more -CH2- atoms constituting the alkylene group represented by SP4 can be replaced by the aforementioned "SP-C", and is particularly preferably selected from -O-, -S-, and -N(R-). 21 )-, -C(=O)-, -C(=S)-, -C(R 22)=C(R 23 -, ynynyl, -Si(R) 24 (R) 25 -, -N=N-, -C(R) 26 )=NN=C(R 27 )-、-C(R 28 At least one group from the group consisting of N- and S(=O)2- is substituted. Wherein, R 21 ~R 28 Each of these can independently represent a hydrogen atom, a halogen atom, a cyano group, a nitro group, or a straight-chain or branched alkyl group having 1 to 10 carbon atoms. Furthermore, the hydrogen atoms contained in one or more -CH2- groups constituting the alkylene group represented by SP4 can be replaced by the aforementioned "SP-H".
[0282] The main chain of SP4 has 10 or more atoms, and from the viewpoint of obtaining a light absorption anisotropic layer with better at least one of superior adhesion and planar uniformity, it is preferably 15 or more, and more preferably 19 or more. Furthermore, from the viewpoint of obtaining a light absorption anisotropic layer with better orientation, the upper limit of the main chain of SP2 is preferably 70 or less, more preferably 60 or less, and particularly preferably 50 or less.
[0283] Here, the "main chain" in SP4 refers to the partial structure required to directly connect L4 and T4, and the "number of atoms in the main chain" refers to the number of atoms constituting the aforementioned partial structure. In other words, the "main chain" in SP4 is the partial structure where the number of atoms connecting L4 and T4 is the shortest. For example, the number of atoms in the main chain of SP4 when it is 3,7-dimethyldecyl is 10, and the number of atoms in the main chain of SP4 when it is 4,6-dimethyldodecyl is 12. Furthermore, in the following formula (4-1), the box represented by the dashed quadrilateral corresponds to SP4, and the number of atoms in the main chain of SP4 (equivalent to the total number of atoms enclosed by the dashed circle) is 11.
[0284] [Chemical Formula 21]
[0285]
[0286] The alkylene group represented by SP4 can be either straight-chain or branched.
[0287] From the viewpoint of obtaining an anisotropic light absorption layer with better orientation, the number of carbon atoms in the alkylene group represented by SP4 is preferably 8 to 80, more preferably 15 to 80, more preferably 25 to 70, and especially preferably 25 to 60.
[0288] From the perspective of obtaining a light absorption anisotropic layer with better adhesion and planar uniformity, one or more -CH2- atoms constituting the alkylene group represented by SP4 are preferably replaced by the above-mentioned "SP-C".
[0289] Furthermore, in the case of having multiple -CH2- groups representing alkylene groups as defined by SP4, from the perspective of obtaining a light absorption anisotropic layer with better adhesion and planar uniformity, it is more preferable that only a portion of the multiple -CH2- groups are replaced by the aforementioned "SP-C".
[0290] In “SP-C”, the preferred selections are -O-, -S-, and -N(R). 21 )-, -C(=O)-, -C(=S)-, -C(R 22 )=C(R 23 -, ynynyl, -Si(R) 24 (R) 25 -, -N=N-, -C(R) 26 )=NN=C(R 27 )-、-C(R 28 At least one group from the group consisting of -O- and -S(=O)2- is preferred, considering the possibility of obtaining a light absorption anisotropic layer with better adhesion and planar uniformity. 21 At least one group selected from the group consisting of -O-, -C(=O)- and -S(=O)2-, particularly preferably selected from -O-, -N(R)-, and -C(=O)-. 21 At least one group from the group consisting of )- and C(=O)-.
[0291] In particular, SP4 is preferably a group comprising at least one of the following groups: alkylene oxide structures comprising one or more -CH2-substituted-O-, ester structures comprising one or more -CH2-CH2-substituted-O- and C(=o)-, and urethane bonds comprising one or more -CH2-CH2-CH2-substituted-O-, -C(=O)-, and NH-, respectively.
[0292] One or more hydrogen atoms in the -CH2- group constituting the alkylene group represented by SP4 can be replaced by the aforementioned "SP-H". In this case, it is sufficient for one or more hydrogen atoms in the -CH2- group to be replaced by "SP-H". That is, it is possible for only one hydrogen atom in the -CH2- group to be replaced by "SP-H", or it is possible for all two hydrogen atoms in the -CH2- group to be replaced by "SP-H".
[0293] In “SP-H”, preferably, at least one group is selected from the group consisting of halogen atom, cyano, nitro, hydroxyl, straight-chain alkyl with 1 to 10 carbon atoms, branched alkyl with 1 to 10 carbon atoms, and haloalkyl with 1 to 10 carbon atoms. More preferably, at least one group is selected from the group consisting of hydroxyl, straight-chain alkyl with 1 to 10 carbon atoms, and branched alkyl with 1 to 10 carbon atoms.
[0294] As described above, T4 represents the same terminal group as T1, preferably a hydrogen atom, methyl, hydroxyl, carboxyl, sulfonic acid, phosphate, borate, amino, cyano, nitro, or a phenyl group that may have substituents, or -L-CL (L represents a single bond or a divalent linker. Specific examples of divalent linkers are the same as those for LW and SPW described above. CL represents a crosslinking group, and examples include groups represented by Q1 or Q2 described above, preferably crosslinking groups represented by formulas (P1) to (P30). As the CL described above, vinyl, butadiene, (meth)acryloyl, (meth)acrylamido, vinyl acetate, fumarate, styrene, vinylpyrrolidone, maleic anhydride, maleimide, vinyl ether, epoxy, or oxetane.
[0295] The epoxy group can be an epoxycycloalkyl group. From the perspective of further improving the effect of the present invention, the number of carbon atoms in the cycloalkyl part of the epoxycycloalkyl group is preferably 3 to 15, more preferably 5 to 12, and especially preferably 6 (i.e., the case where the epoxycycloalkyl group is an epoxycyclohexyl group).
[0296] Examples of substituents for the oxetine group include alkyl groups having 1 to 10 carbon atoms; however, for better performance of the present invention, alkyl groups having 1 to 5 carbon atoms are preferred. The alkyl group used as a substituent for the oxetine group can be linear or branched; however, for better performance of the present invention, a linear form is preferred.
[0297] Examples of substituents for phenyl groups include borate, sulfonic acid, vinyl, and amino groups. From the perspective of further improving the effects of the present invention, borate is preferred.
[0298] As specific examples of the repeating unit (4), the following structures can be given, but the present invention is not limited to these. In addition, in the following specific examples, n1 represents an integer of 2 or more, and n2 represents an integer of 1 or more.
[0299] [Chemical Formula 22]
[0300]
[0301] The content of the repeating unit (4) is preferably 2 to 20% by mass, more preferably 3 to 18% by mass, relative to all repeating units (100% by mass) in the polymeric liquid crystal compound. If the content of the repeating unit (4) is 2% by mass or more, a light absorption anisotropic layer with better adhesion can be obtained. Furthermore, if the content of the repeating unit (4) is 20% by mass or less, a light absorption anisotropic layer with better planar uniformity can be obtained.
[0302] The polymeric liquid crystal compound may contain only one repeating unit (4) or two or more repeating units (4). When two or more repeating units (4) are contained, the content of the repeating unit (4) refers to the total content of the repeating units (4).
[0303] (Repeated unit (5))
[0304] From the viewpoint of planar uniformity, the polymeric liquid crystal compound can contain repeating units (5) introduced by polymerizing a multifunctional monomer. In particular, in order to suppress the decrease in orientation degree while improving planar uniformity, it is preferable to contain 10% by mass or less of repeating units (5) introduced by polymerizing the multifunctional monomer. Thus, the reason for suppressing the decrease in orientation degree and improving planar uniformity by containing 10% by mass or less of repeating units (5) is speculated as follows.
[0305] The repeating unit (5) is a unit introduced into the polymeric liquid crystal compound to facilitate the polymerization of multifunctional monomers. Therefore, it is considered that the polymeric liquid crystal compound contains a high molecular weight body with a three-dimensional cross-linked structure formed by the repeating unit (5). Here, since the content of the repeating unit (5) is small, it is considered that the content of the high molecular weight body containing the repeating unit (5) is low.
[0306] Thus, it is speculated that by the presence of a small amount of high molecular weight bodies with three-dimensional cross-linked structures, the repulsion of the liquid crystal composition is suppressed, thereby obtaining a light absorption anisotropic layer with excellent planar uniformity.
[0307] Furthermore, since the content of high molecular weight polymers is small, it is speculated that this can maintain the effect of inhibiting the decrease in orientation.
[0308] The repeating unit (5) introduced by the polymerization of the multifunctional monomer is preferably a repeating unit represented by the following formula (5).
[0309] [Chemical Formula 23]
[0310]
[0311] In equation (5), PC5A and PC5B represent the main chain of repeating units, more specifically, the same structure as PC1 in equation (1) above; L5A and L5B represent single bonds or divalent linkers, more specifically, the same structure as L1 in equation (1) above; SP5A and SP5B represent spacer groups, more specifically, the same structure as SP1 in equation (1) above; MG5A and MG5B represent mesocrystalline structures, more specifically, the same structure as the mesocrystalline group MG in equation (LC) above; and a and b represent integers 0 or 1.
[0312] PC5A and PC5B can be the same group or different groups. Considering the further improvement of the orientation degree of the light absorption anisotropy layer, the same group is preferred.
[0313] L5A and L5B can both be single bonds, or they can be the same group, or they can be different groups. However, considering the further improvement of the orientation degree of the light absorption anisotropy layer, they are both preferably single bonds or the same group, and more preferably the same group.
[0314] SP5A and SP5B can both be single bonds, or they can be the same group, or they can be different groups. However, considering the further improvement of the orientation degree of the light absorption anisotropy layer, they are both preferably single bonds or the same group, and more preferably the same group.
[0315] Here, the same group in formula (5) refers to groups with the same chemical structure regardless of their bonding orientation. For example, SP5A is *-CH2-CH2-O-** (* indicates the bonding position with L5A, and ** indicates the bonding position with MG5A.) and SP5B is *-O-CH2-CH2-** (* indicates the bonding position with MG5B, and ** indicates the bonding position with L5B.) which also constitutes the same group.
[0316] a and b are independent integers of 0 or 1, and from the perspective of further improving the orientation degree of the light absorption anisotropic layer, 1 is preferred.
[0317] a and b can be the same or different, but considering the further improvement of the orientation degree of the light absorption anisotropic layer, 1 is preferred.
[0318] From the perspective of further improving the orientation degree of the light-absorbing anisotropic layer, the total of a and b is preferably 1 or 2 (i.e., the repeating unit represented by formula (5) has a mesocrystalline group), more preferably 2.
[0319] Considering further improvements in the orientation degree of the light absorption anisotropy layer, from -(MG5A) a -(MG5B) b The structure indicated by - preferably has a ring structure. In this case, considering further improvement in the orientation degree of the light-absorbing anisotropic layer, -(MG5A2) a -(MG5B) b - The number of ring structures in the partial structure is preferably 2 or more, more preferably 2 to 8, even more preferably 2 to 6, and especially preferably 2 to 4.
[0320] From the perspective of further improving the orientation degree of the light absorption anisotropic layer, the mesocrystalline groups represented by MG5A and MG5B each preferably contain one or more ring structures, preferably two to four, more preferably two to three, and especially preferably two.
[0321] Specific examples of cyclic structures include aromatic hydrocarbon groups, heterocyclic groups, and alicyclic groups, with aromatic hydrocarbon groups and alicyclic groups being preferred.
[0322] MG5A and MG5B can be the same group or different groups. From the perspective of further improving the orientation degree of the light absorption anisotropy layer, the same group is preferred.
[0323] From the viewpoints of liquid crystal properties, liquid crystal phase transition temperature adjustment, raw material availability and synthetic suitability, and the viewpoint of superior effects of the present invention, the mesocrystalline group MG in the above formula (LC) is preferred as the mesocrystalline group represented by MG5A and MG5B.
[0324] In particular, the repeating unit (5) preferably has PC5A and PC5B as the same group, L5A and L5B as single bonds or the same group, SP5A and SP5B as single bonds or the same group, and MG5A and MG5B as the same group. As a result, the orientation degree of the light absorption anisotropy layer is further improved.
[0325] The content of the repeating unit (5) is preferably 10% by mass or less, more preferably 0.001 to 5% by mass, and even more preferably 0.05 to 3% by mass, relative to the content of all repeating units (100% by mass) of the polymeric liquid crystal compound.
[0326] The polymeric liquid crystal compound may contain only one repeating unit (5) or two or more. When two or more repeating units (5) are contained, it is preferable that their total amount is within the above-mentioned range.
[0327] (Star-shaped polymer)
[0328] The liquid crystal compound can be a star polymer. In this invention, a star polymer refers to a polymer having three or more polymer chains extending from a core, specifically represented by the following formula (6).
[0329] As a liquid crystal polymer, the star-shaped polymer represented by formula (6) has high solubility (excellent solubility in solvents) and can form a light-absorbing anisotropic layer with high orientation.
[0330] [Chemical Formula 24]
[0331]
[0332] In equation (6), n A n represents an integer of 3 or higher, preferably an integer of 4 or higher. A The upper limit is not limited to this, but it is usually below 12, preferably below 6.
[0333] Each of the plurality of PIs independently represents a polymer chain containing any one of the repeating units represented by equations (1), (21), (22), (3), (4), and (5) above. However, at least one of the plurality of PIs represents a polymer chain containing a repeating unit represented by equation (1) above.
[0334] A represents the atomic group that forms the core of the star-shaped polymer. Specific examples of A include paragraphs
[0052] to
[0058] of Japanese Patent Application Publication No. 2011-074280, paragraphs
[0017] to
[0021] of Japanese Patent Application Publication No. 2012-189847, paragraphs
[0012] to
[0024] of Japanese Patent Application Publication No. 2013-031986, and paragraphs
[0118] to
[0142] of Japanese Patent Application Publication No. 2014-104631, in which hydrogen atoms have been removed from the thiol group of a polyfunctional thiol compound. In this case, A and PI are bonded via a thioether bond.
[0335] The polyfunctional thiol compound that becomes the source of A preferably has 3 or more thiol groups, more preferably 4 or more. The upper limit for the number of thiol groups in the polyfunctional thiol compound is generally 12 or less, preferably 6 or less.
[0336] The following are specific examples of polyfunctional thiols.
[0337] [Chemical Formula 25]
[0338]
[0339] From the perspective of improving orientation, polymeric liquid crystal compounds can be thermotropic liquid crystals and crystalline polymers.
[0340] (Thermotropic liquid crystals)
[0341] Thermotropic liquid crystals are liquid crystals that exhibit a transition to a liquid crystal phase through temperature changes.
[0342] The specific compound is a thermotropic liquid crystal that can display either a nematic phase or a smectic phase. Considering that the orientation degree of the light-absorbing anisotropic layer becomes higher and the haze is less likely to be observed (the haze becomes better), it is preferable to display at least a nematic phase.
[0343] From the perspective that the orientation degree of the light-absorbing anisotropic layer becomes higher and the haze is less likely to be observed, the temperature range of the nematic phase is preferably room temperature (23°C) to 450°C, and more preferably 40°C to 400°C from the viewpoint of processing or manufacturing suitability.
[0344] (Crystall polymer)
[0345] Crystalline polymers are polymers that exhibit a transformation to a crystalline layer through temperature changes. In addition to exhibiting a transformation to a crystalline layer, crystalline polymers can also exhibit a glass transition.
[0346] From the perspective of increasing the orientation degree of the light absorption anisotropic layer and making the haze less difficult to observe, the crystalline polymer is preferably a polymeric liquid crystal compound that undergoes a transition from a crystalline phase to a liquid crystal phase upon heating (with the possibility of a glass transition in between) or a polymeric liquid crystal compound that undergoes a transition from a crystalline phase to a crystalline phase upon cooling after being heated to a liquid crystal state (with the possibility of a glass transition in between).
[0347] In addition, the crystallinity of polymeric liquid crystal compounds is evaluated in the following manner.
[0348] Two anisotropic light-absorbing layers of an optical microscope (NIKON Co., Ltd. ECLIPSE E600POL) were arranged orthogonally, with a sample stage placed between them. A small amount of a polymeric liquid crystal compound was then placed on a glass slide, which was then placed on a heated stage on the sample stage. While observing the sample state, the temperature of the heated stage was increased to the temperature at which the polymeric liquid crystal compound exhibited liquid crystal properties, thus precipitating the polymeric liquid crystal compound into a liquid crystal state. After the polymeric liquid crystal compound entered the liquid crystal state, the behavior of the liquid crystal phase transition was observed while the temperature of the heated stage was gradually decreased, and the temperature of the liquid crystal phase transition was recorded. In addition, the transition temperatures of the polymeric liquid crystal compound exhibiting multiple liquid crystal phases (e.g., nematic and smectic phases) were also recorded.
[0349] Next, approximately 5 mg of the polymeric liquid crystal compound sample was placed in an aluminum dish, covered, and fixed in a differential scanning calorimeter (DSC) (using an empty aluminum dish as a reference). The sample was heated to the temperature at which the polymeric liquid crystal compound exhibited the liquid crystal phase as determined above, and then held at that temperature for 1 minute. Then, the temperature was lowered at a rate of 10 °C / min while performing calorimetric measurements. The calorimetric peak was confirmed from the obtained calorimetric spectrum.
[0350] As a result, when a heating peak is observed at temperatures other than the liquid crystal phase transition temperature, the heating peak is a peak generated through crystallization, which means that the polymer liquid crystal compound has crystallinity.
[0351] On the other hand, if no heating peak is observed at temperatures other than the liquid crystal phase transition temperature, it can be said that the polymeric liquid crystal compound does not have crystallinity.
[0352] There are no particular limitations on the method for obtaining crystalline polymers. As a specific example, it is preferable to use a method that uses a polymeric liquid crystal compound containing the above-mentioned repeating unit (1), and more preferably, a method that uses a preferred method among polymeric liquid crystal compounds containing the above-mentioned repeating unit (1).
[0353] Crystallization temperature
[0354] From the perspective of achieving a higher degree of orientation in the light-absorbing anisotropic layer and making haze less observable, the crystallization temperature of the polymeric liquid crystal compound is preferably -50°C or higher and less than 150°C, more preferably 120°C or lower, even more preferably -20°C or higher and less than 120°C, and particularly preferably 95°C or lower. From the viewpoint of reducing haze, the crystallization temperature of the aforementioned polymeric liquid crystal compound is preferably below 150°C.
[0355] In addition, the crystallization temperature is the temperature of the heat peak generated by crystallization in the above DSC.
[0356] (molecular weight)
[0357] From the perspective of further improving the effects of the present invention, the weight-average molecular weight (Mw) of the polymeric liquid crystal compound is preferably 1,000 to 500,000, more preferably 2,000 to 300,000. If the Mw of the polymeric liquid crystal compound is within the above range, the polymeric liquid crystal compound becomes easier to process.
[0358] In particular, from the viewpoint of suppressing cracking during coating, the weight-average molecular weight (Mw) of the polymeric liquid crystal compound is preferably 10,000 or more, and more preferably 10,000 to 300,000.
[0359] Furthermore, from the viewpoint of temperature tolerance of orientation, the weight-average molecular weight (Mw) of the polymeric liquid crystal compound is preferably less than 10,000, and preferably more than 2,000 and less than 10,000.
[0360] In this invention, the weight-average molecular weight and number-average molecular weight are values determined by gel permeation chromatography (GPC).
[0361] • Solvent (eluent): N-methylpyrrolidone
[0362] • Device Name: TOSOH HLC-8220GPC
[0363] • Column: Connect 3 TOSOH TSKgelSuperAWM-H (6mm×15cm) for use.
[0364] Column temperature: 25℃
[0365] • Sample concentration: 0.1% by mass
[0366] • Flow rate: 0.35 mL / min
[0367] • Calibration curves: Calibration curves were obtained using seven samples of TSK standard polystyrene prepared based on the TOSOH CORPORATION standard, with Mw = 2,800,000–1,050 (Mw / Mn = 1.03–1.06).
[0368] The liquid crystal properties of a polymeric liquid crystal compound can exhibit either nematic or smectic properties, but preferably at least nematic.
[0369] The preferred temperature range for the nematic phase is 0°C to 450°C, and from the viewpoint of processing or manufacturing suitability, it is preferably 30°C to 400°C.
[0370] <Content>
[0371] From the viewpoint of achieving better results with the present invention, the content of the liquid crystal compound relative to the total solid content (100% by mass) of the liquid crystal composition is preferably 10 to 97% by mass, more preferably 40 to 95% by mass, and even more preferably 60 to 95% by mass.
[0372] When the liquid crystal compound contains a polymeric liquid crystal compound, the content of the polymeric liquid crystal compound relative to the total mass (100 parts by mass) of the liquid crystal compound is preferably 10 to 99% by mass, more preferably 30 to 95% by mass, and even more preferably 40 to 90% by mass.
[0373] When the liquid crystal compound contains a low-molecular-weight liquid crystal compound, the content of the low-molecular-weight liquid crystal compound relative to the total mass (100 parts by mass) of the liquid crystal compound is preferably 1 to 90% by mass, more preferably 5 to 70% by mass, and even more preferably 10 to 60% by mass.
[0374] When the liquid crystal compound includes both high molecular weight liquid crystal compound and low molecular weight liquid crystal compound, from the perspective of better performance of the present invention, the mass ratio of the content of low molecular weight liquid crystal compound to the content of high molecular weight liquid crystal compound (low molecular weight liquid crystal compound / high molecular weight liquid crystal compound) is preferably 5 / 95 to 70 / 30, more preferably 10 / 90 to 50 / 50.
[0375] Here, "solid components in liquid crystal compositions" refers to components other than solvents. Specific examples of solid components include the aforementioned liquid crystal compounds, dichroic substances, polymerization initiators, surface modifiers, etc.
[0376] <Dichromatic substances>
[0377] The liquid crystal composition also contains dichroic substances.
[0378] In this invention, dichroic substances refer to pigments whose absorbance varies with direction. Dichroic substances may or may not exhibit liquid crystal properties.
[0379] There are no particular limitations on dichroic substances. Examples include visible light absorbing substances (dichroic pigments), luminescent substances (fluorescent substances, phosphorescent substances), ultraviolet light absorbing substances, infrared light absorbing substances, nonlinear optical substances, carbon nanotubes, and inorganic substances (such as quantum rods). Previously known dichroic substances (dichroic pigments) can be used.
[0380] Specifically, examples include paragraphs
[0067] to
[0071] of Japanese Patent Application Publication No. 2013-228706, paragraphs
[0008] to
[0026] of Japanese Patent Application Publication No. 2013-227532, paragraphs
[0008] to
[0015] of Japanese Patent Application Publication No. 2013-209367, paragraphs
[0045] to
[0058] of Japanese Patent Application Publication No. 2013-14883, paragraphs
[0012] to
[0029] of Japanese Patent Application Publication No. 2013-101328, paragraphs
[0009] to
[0017] of Japanese Patent Application Publication No. 2013-37353, and paragraphs
[0051] to
[0065] . Paragraphs
[0049] to
[0073] of Japanese Patent Application Publication No. 2012-63387, Paragraphs
[0016] to
[0018] of Japanese Patent Application Publication No. Hei 11-305036, Paragraphs
[0009] to
[0011] of Japanese Patent Application Publication No. 2001-133630, Paragraphs
[0030] to
[0169] of Japanese Patent Application Publication No. 2011-215337, Paragraphs
[0021] to
[0075] of Japanese Patent Application Publication No. 2010-106242, Paragraphs
[0011] to
[0025] of Japanese Patent Application Publication No. 2010-215846, Paragraphs
[0017] to
[0069] of Japanese Patent Application Publication No. 2011- Paragraphs
[0013] to
[0133] of Japanese Patent Application Publication No. 213610, paragraphs
[0074] to
[0246] of Japanese Patent Application Publication No. 2011-237513, paragraphs
[0005] to
[0051] of Japanese Patent Application Publication No. 2016-006502, paragraphs
[0014] to
[0032] of Japanese Patent Application Publication No. 2018-053167, paragraphs
[0014] to
[0033] of Japanese Patent Application Publication No. 2020-11716, paragraphs
[0005] to
[0041] of International Publication No. 2016 / 060173, paragraphs
[0008] to
[0062] of International Publication No. 2016 / 136561, and International Publication No. 2017 / 154835. Paragraphs
[0014] to
[0033] , paragraphs
[0014] to
[0033] of International Publication No. 2017 / 154695, paragraphs
[0013] to
[0037] of International Publication No. 2017 / 195833, paragraphs
[0014] to
[0034] of International Publication No. 2018 / 164252, paragraphs
[0021] to
[0030] of International Publication No. 2018 / 186503, paragraphs
[0043] to
[0063] of International Publication No. 2019 / 189345, paragraphs
[0043] to
[0085] of International Publication No. 2019 / 225468, and paragraphs
[0050] to
[0074] of International Publication No. 2020 / 004106.The dichroic substance described in paragraphs
[0015] to
[0038] of International Publication No. 2021 / 044843.
[0381] In this invention, two or more dichroic materials may be used simultaneously. For example, from the viewpoint of making the formed light absorption anisotropic layer close to black, it is preferable to use at least one dichroic material with a maximum absorption wavelength in the wavelength range of 370 to 550 nm and at least one dichroic material with a maximum absorption wavelength in the wavelength range of 500 to 700 nm.
[0382] As described above, the content of the dichroic substance is 8.0% by mass or more relative to the total solid content of the liquid crystal composition. However, considering the need to further improve the visual recognition of the image from the desired direction and to further adequately block images from other directions, it is preferably 13.0% by mass or more relative to the total solid content of the liquid crystal composition, and more preferably 13 to 50% by mass. In addition, when multiple dichroic substances are used simultaneously, the total amount of the multiple dichroic substances is preferably within the above-described range.
[0383] <Orientation Agent>
[0384] The liquid crystal composition also contains an alignment agent.
[0385] As orientation agents, examples include those described in paragraphs
[0042] to
[0076] of Japanese Patent Application Publication No. 2013-543526, paragraphs
[0089] to
[0097] of Japanese Patent Application Publication No. 2016-523997, and paragraphs
[0153] to
[0170] of Japanese Patent Application Publication No. 2020-076920. These can be used alone or in combination with two or more.
[0386] In this invention, considering the reduced temperature dependence of the transmission axis center axis angle θ, it is preferable that the liquid crystal compound is a thermotropic liquid crystal, and that the alignment agent is an alignment agent capable of setting the phase transition reduction temperature ΔTF defined by the following formula (TF) to -10.0℃ to -0.1℃, more preferably an alignment agent capable of setting the phase transition reduction temperature ΔTF defined by the following formula (TF) to -7.0℃ to -0.1℃.
[0387] ΔTF=T1-T2……(TF)
[0388] Here, in the above formula (TF), T1 represents the phase transition temperature of the liquid and liquid crystal in a liquid crystal composition t1 containing a thermotropic liquid crystal compound and a dichroic substance but not an alignment agent.
[0389] Furthermore, T2 represents the phase transition temperature of the liquid and the liquid crystal in the mixture t2, which contains 2.0 parts by mass of alignment agent relative to 100 parts by mass of the liquid crystal composition t1.
[0390] The detailed reason why the temperature dependence of the transmission axis center axis angle θ decreases when using an orientation agent that can set the phase transition reduction temperature ΔTF to -10.0℃ to -0.1℃ is not yet clear, but the inventors speculate as follows.
[0391] First, it is believed that the orientation agent is biased near the interface on the lower side of the light-absorbing anisotropic layer.
[0392] Furthermore, it is believed that the miscibility / incompatibility of liquid crystal compounds and dichroic substances with orientation agents sometimes changes depending on temperature or liquid crystal phase transition, and due to this change, the tilt angle θ near the interface on the lower layer side changes.
[0393] Therefore, the alignment agent that can set the phase transition reduction temperature ΔTF to -10.0℃ to -0.1℃ has low affinity for liquid crystal compounds and dichroic substances and small temperature-induced changes in miscibility / immiscibility. Thus, it is believed that the temperature dependence of the transmission axis central axis angle θ is reduced.
[0394] In this invention, considering the reasons that the visual recognition of the image from the desired direction is further improved and the image from other directions can be further sufficiently blocked, the orientation agent is preferably an onium compound represented by the following formula (B1).
[0395] [Chemical Formula 26]
[0396]
[0397] In the above formula (B1), ring A represents a quaternary ammonium ion composed of a nitrogen-containing heterocycle.
[0398] Furthermore, X represents an anion.
[0399] Furthermore, L 1 This indicates a divalent linker.
[0400] Furthermore, L 2 This indicates a single bond or a divalent linker.
[0401] Furthermore, Y 1 This indicates a divalent linker with a 5- or 6-membered ring as part of the structure.
[0402] Furthermore, Z indicates that an alkylene group with 2 to 20 carbon atoms serves as a divalent linker in the partial structure.
[0403] Furthermore, P 1 and P 2Each of these represents a monovalent substituent that has a polymerizable olefinic unsaturated bond.
[0404] Ring A represents a quaternary ammonium ion composed of a nitrogen-containing heterocycle. Examples of ring A include pyridine rings, methylpyridine rings, 2,2'-bipyridinyl rings, 4,4'-bipyridinyl rings, 1,10-phenanthroline rings, quinoline rings, oxazole rings, thiazole rings, imidazole rings, pyrazine rings, triazole rings, tetrazolium rings, etc., with quaternary imidazole ions and quaternary pyridinium ions being preferred.
[0405] X represents an anion. Examples of X include halide anions (e.g., fluoride, chloride, bromide, iodide, etc.), sulfonate ions (e.g., methanesulfonate, trifluoromethanesulfonate, methyl sulfate, vinylsulfonate, allylsulfonate, p-toluenesulfonate, p-chlorobenzenesulfonate, p-vinylbenzenesulfonate, 1,3-benzenedisulfonate, 1,5-naphthalenedisulfonate, 2,6-naphthalenedisulfonate, etc.), sulfate ions, carbonate ions, nitrate ions, thiocyanate ions, perchlorate ions, tetrafluoroborate ions, picric acid ions, acetate ions, benzoate ions, p-vinylbenzoate ions, formic acid ions, trifluoroacetate ions, phosphate ions (e.g., hexafluorophosphate ions), and hydroxide ions. Halogen anions, sulfonate ions, and hydroxide ions are preferred. Furthermore, chloride ions, bromide ions, iodide ions, methanesulfonate ions, vinylsulfonate ions, p-toluenesulfonate ions, and p-vinylbenzenesulfonate ions are particularly preferred.
[0406] L 1 Indicates a divalent linker. As L 1 Examples include divalent linkages with 1 to 20 carbon atoms, composed of combinations of alkylene, -O-, -S-, -CO-, -SO2-, -NRa- (where Ra is an alkyl or hydrogen atom with 1 to 5 carbon atoms), alkenyl, ynylene, or arylene. 1 Preferably, the carbon atoms are -AL-, -O-AL-, -CO-O-AL-, or -O-CO-AL-, with 1 to 10 carbon atoms; more preferably, -AL- or -O-AL-, with 1 to 10 carbon atoms; and most preferably, -AL- or -O-AL-, with 1 to 5 carbon atoms. Additionally, AL represents an alkylene group.
[0407] L2 represents a single bond or a divalent linker. As L... 2Examples include divalent linkages with 1 to 10 carbon atoms, single bonds, and combinations of alkylene, -O-, -S-, -CO-, -SO2-, -NRa- (where Ra is an alkyl or hydrogen atom with 1 to 5 carbon atoms), alkenyl, ynylene, or arylene groups; -O-, -O-CO-, -CO-O-, -O-AL-O-, -O-AL-O-CO-, -O-AL-CO-O-, -CO-O-AL-O-, -CO-O-AL-O-CO-, -CO-O-AL-CO-O-, -O-CO-AL-O-, -O-CO-AL-O-, -O-CO-AL-CO-O-, etc. Additionally, AL represents alkylene. L2 is preferably a single bond with 1 to 10 carbon atoms, such as -AL-, -O-AL-, or -NRa-AL-O-, further preferably a single bond with 1 to 5 carbon atoms, such as -AL-, -O-AL-, or -NRa-AL-O-, and most preferably a single bond with 1 to 5 carbon atoms, such as -O-AL- or -NRa-AL-O-.
[0408] Y 1 This indicates a divalent linker with a 5- or 6-membered ring as a partial structure. As Y... 1 Examples of heterocyclic rings include cyclohexyl rings, aromatic rings, and heterocyclic rings. Examples of aromatic rings include benzene rings, indene rings, naphthalene rings, fluorene rings, phenanthrene rings, anthracene rings, biphenyl rings, and pyrene rings, with benzene rings, biphenyl rings, and naphthalene rings being particularly preferred. Examples of heteroatoms constituting the heterocyclic ring include nitrogen atoms, oxygen atoms, and sulfur atoms; examples include furan rings, thiophene rings, pyrrole rings, pyrrolin rings, pyrrolidinyl rings, oxazole rings, isoxazole rings, thiazole rings, isothiazole rings, imidazole rings, imidazoleline rings, imidazolealidyl rings, pyrazolidine rings, triazole rings, furazonium rings, tetrazolium rings, pyran rings, dioxane rings, dithiohexacyclohexane rings, thipenan rings, pyridine rings, pyridine rings, oxazine rings, morpholine rings, thiazine rings, pyridazine rings, pyrimidine rings, pyrazine rings, piperazine rings, and triazine rings. The heterocyclic ring is preferably a 6-membered ring. Having Y 1 The 5- or 6-membered rings represented as divalent linkers in the partial structure may also have substituents (e.g., the substituent W mentioned above).
[0409] By Y 1 The divalent linker represented is preferably a divalent linker having two or more 5- or 6-membered rings, and more preferably a divalent linker having two or more rings connected by the linker. Examples of linkers include those represented by L1 and L2, or -C≡C-, -CH=CH-, -CH=N-, -N=CH-, -N=N-, etc.
[0410] Z has an alkylene group having 2 to 20 carbon atoms as a partial structure, representing a divalent linker composed of a combination with -O-, -S-, -CO-, or -SO2-, and the alkylene group may have substituents. Examples of the aforementioned divalent linker include alkeneoxy groups and polyalkyleneoxy groups. The alkylene group represented by Z more preferably has 2 to 16 carbon atoms, further preferably 2 to 12, and particularly preferably 2 to 8.
[0411] P1 and P2 each independently represent a monovalent substituent having a polymerizable olefinic unsaturated group. Examples of the aforementioned monovalent substituents having polymerizable olefinic unsaturated groups include the following formulas (M-1) to (M-8). That is, the monovalent substituent having a polymerizable olefinic unsaturated group can be a substituent composed only of vinyl groups, such as (M-8).
[0412] [Chemical Formula 27]
[0413]
[0414] In formulas (M-3) and (M-4), R represents a hydrogen atom or an alkyl group, preferably a hydrogen atom or a methyl group. Among the formulas (M-1) to (M-8) above, (M-1), (M-2), and (M-8) are preferred, more preferably (M-1) or (M-8). In particular, (M-1) is preferred as P1. Furthermore, (M-1) or (M-8) is preferred as P2; in compounds where ring A is a quaternary imidazolium ion, P2 is preferably (M-8) or (M-1); in compounds where ring A is a quaternary pyridinium ion, P2 is preferably (M-1).
[0415] Examples of onium compounds represented by the above formula (B1) include the onium salts described in paragraphs 0052 to 0058 of Japanese Patent Application Publication No. 2012-208397, the onium salts described in paragraphs 0024 to 0055 of Japanese Patent Application Publication No. 2008-026730, and the onium salts described in Japanese Patent Application Publication No. 2002-37777.
[0416] In this invention, considering the reasons that the visual recognition of the image from the desired direction is further improved and the image from other directions can be further sufficiently blocked, the orientation agent is preferably a boric acid compound represented by the following formula (B2).
[0417] [Chemical Formula 28]
[0418]
[0419] In (B2) above, R 1 and R 2 Each can independently represent a hydrogen atom, an aliphatic hydrocarbon group that may have substituents, an aryl group that may have substituents, or a heterocyclic group that may have substituents.
[0420] Furthermore, R 3 Indicates a substituent.
[0421] As R 1 and R 2 Examples of aliphatic hydrocarbon groups represented in one manner include substituted or unsubstituted straight-chain or branched alkyl groups (e.g., methyl, ethyl, isopropyl, etc.) having 1 to 20 carbon atoms, substituted or unsubstituted cyclic alkyl groups (e.g., cyclohexyl, etc.) having 3 to 20 carbon atoms, and alkenyl groups (e.g., vinyl, etc.) having 2 to 20 carbon atoms.
[0422] Furthermore, as R 1 and R 2 Examples of aryl groups represented in one manner include substituted or unsubstituted phenyl groups (e.g., phenyl, tolyl, etc.) with 6 to 20 carbon atoms, and substituted or unsubstituted naphthyl groups with 10 to 20 carbon atoms.
[0423] Furthermore, as R 1 and R 2 The heterocyclic group represented in one manner, for example, includes substituted or unsubstituted 5- or 6-membered ring groups containing at least one heteroatom (e.g., nitrogen atom, oxygen atom, sulfur atom, etc.), specifically pyridyl, imidazolyl, furanyl, piperidinyl, morpholinyl, etc.
[0424] R 1 and R 2 They can be connected to form a loop, for example, it can be R 1 and R 2 The isopropyl group is linked to form a 4,4,5,5-tetramethyl-1,3,2-dioxane ring.
[0425] R 1 and R 2 Preferably, it is a hydrogen atom, a straight-chain or branched alkyl group having 1 to 3 carbon atoms, and the linking of these to form a ring, more preferably a hydrogen atom.
[0426] As R 3 The substituents indicated are preferably substituents containing functional groups capable of bonding with (meth)acryloyl groups.
[0427] Here, as functional groups capable of bonding with (meth)acryloyl groups, examples include vinyl, acrylate, methacrylate, acrylamide, styrene, vinyl ketone, butadiene, vinyl ether, ethylene oxide, aziridinyl, oxetyl, etc., wherein vinyl, acrylate, methacrylate, styrene, ethylene oxide, or oxetyl are preferred, and vinyl, acrylate, acrylamide, or styrene are more preferred.
[0428] As R 3 Preferably, it is a substituted or unsubstituted aliphatic hydrocarbon group, aryl group or heterocyclic group having a functional group capable of bonding with (meth)acryloyl group.
[0429] Examples of aliphatic hydrocarbon groups include substituted or unsubstituted straight-chain or branched alkyl groups with 1 to 30 carbon atoms (e.g., methyl, ethyl, isopropyl, n-propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, hexadecyl, octadecyl, eicosyl, isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, neopentyl, 1-methylbutyl, isohexyl, 2-methylhexyl, etc.), substituted or unsubstituted cyclic alkyl groups with 3 to 20 carbon atoms (e.g., cyclopentyl, cyclohexyl, 1-adamantyl, 2-norbornyl, etc.), and alkenyl groups with 2 to 20 carbon atoms (e.g., vinyl, 1-propenyl, 1-butenyl, 1-methyl-1-propenyl, etc.).
[0430] Examples of aryl groups include substituted or unsubstituted phenyl groups with 6 to 50 carbon atoms (e.g., phenyl, tolyl, styryl, 4-benzoyloxyphenyl, 4-phenoxycarbonylphenyl, 4-biphenyl, 4-(4-octyloxybenzoyloxy)phenoxycarbonylphenyl, etc.) and substituted or unsubstituted naphthyl groups with 10 to 50 carbon atoms (e.g., unsubstituted naphthyl groups, etc.).
[0431] As a heterocyclic group, it is, for example, a substituted or unsubstituted 5- or 6-membered ring group containing at least one heteroatom (e.g., nitrogen atom, oxygen atom, sulfur atom), such as pyrrole, furan, thiophene, pyrazole, imidazole, diazole, oxazole, isoxazole, oxadiazole, thiazole, thiadiazole, indole, carbazole, benzofuran, dibenzofuran, thiain, dibenzothiophene, indazole, benzimidazole, aminoanion, benziisoxazole, benzoxazole, benzothiazole, purine, pyridine, pyridazine, pyrimidine, pyrazine, triazine, quinoline, acridine, isoquinoline, phthalazine, quinazoline, quinoxaline, naphthidine, phenanthroline, pteridine, morpholine, piperidine, etc.
[0432] As a boron oxide compound represented by the above formula (B2), for example, the boron oxide compound represented by general formula (I) described in paragraphs 0023 to 0032 of Japanese Patent Application Publication No. 2008-225281 can be cited.
[0433] As for the compound represented by the above formula (B2), the compounds exemplified below are also preferred.
[0434] [Chemical Formula 29]
[0435]
[0436] In this invention, considering the reasons that the visual recognition of the image from the desired direction is further improved and the image from other directions can be further sufficiently blocked, it is preferable that the content of the orientation agent satisfies the following formula (C).
[0437] 0.010≤Ct / FT≤0.020……(C)
[0438] Here, in the above formula (C), Ct represents the content (mass%) of the alignment agent relative to the total solid content of the liquid crystal composition.
[0439] Furthermore, FT represents the film thickness (μm) of the light-absorbing anisotropic layer.
[0440] The reasons why the above-mentioned effect can be obtained when the content of the above-mentioned orientation agent satisfies the above formula (C) are not yet clear, but the inventors speculate as follows.
[0441] First, as mentioned above, it is believed that the alignment agent is biased near the interface on the lower side of the light-absorbing anisotropic layer and controls the tilt angle of the liquid crystal compound and dichroic material near the interface.
[0442] Therefore, it is believed that the amount of orientation agent biased near the interface on the lower side of the light-absorbing anisotropic layer varies with the film thickness.
[0443] Therefore, it is believed that by satisfying the above equation (C), the control of the tilt angle becomes easier, thus further improving the visual recognition of the image from the desired direction and enabling more sufficient occlusion of the image from other directions.
[0444] On the other hand, the content of the above-mentioned alignment agent is preferably 0.01 to 0.1 parts by mass relative to 100 parts by mass of the total liquid crystal compound and dichroic substance contained in the liquid crystal composition, and more preferably 0.03 to 0.08 parts by mass.
[0445] Solvent
[0446] From an operability and other point of view, the liquid crystal composition preferably contains a solvent.
[0447] Examples of solvents include ketones (e.g., acetone, 2-butanone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, acetylacetone, etc.), ethers (e.g., dioxane, tetrahydrofuran, tetrahydropyran, dioxolane, tetrahydrofuran alcohol, cyclopentylmethyl ether, dibutyl ether, etc.), aliphatic hydrocarbons (e.g., hexane, etc.), alicyclic hydrocarbons (e.g., cyclohexane, etc.), aromatic hydrocarbons (e.g., benzene, toluene, xylene, tetrahydronaphthalene, trimethylbenzene, etc.), carbon halogens (e.g., dichloromethane, chloroform, dichloroethane, dichlorobenzene, 1,1,2,2-tetrachloroethane, chlorotoluene, etc.), and esters (e.g., methyl acetate, ethyl acetate, butyl acetate, diethyl carbonate, ethyl acetoacetate, n-amyl acetate, ethyl benzoate, benzyl benzoate, butyl carbitol acetate). Organic solvents such as diethylene glycol monoethyl ether acetate, isoamyl acetate, etc., alcohols (e.g., ethanol, isopropanol, butanol, cyclohexanol, furfuryl alcohol, 2-ethylhexanol, octanol, benzyl alcohol, ethanolamine, ethylene glycol, propylene glycol, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, etc.), phenols (e.g., phenol, cresol, etc.), cellosolves (e.g., methyl cellosolve, ethyl cellosolve and 1,2-dimethoxyethane, etc.), cellosolve acetates, sulfoxides (e.g., dimethyl sulfoxide, etc.), amides (e.g., dimethylformamide and dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, 1,3-dimethyl-2-imidazolium ketone, etc.), and heterocyclic compounds (e.g., pyridine, 2,6-dimethylpyridine, etc.) as well as water.
[0448] These solvents can be used individually or in combination with two or more solvents.
[0449] When the liquid crystal composition contains a solvent, the solvent content relative to the total mass (100% by mass) of the liquid crystal composition is preferably 60 to 99.5% by mass, more preferably 70 to 99% by mass, and particularly preferably 75 to 98% by mass.
[0450] <Polymerization initiator>
[0451] Liquid crystal compositions may contain polymerization initiators.
[0452] There are no particular restrictions on the type of polymerization initiator, but photosensitive compounds, i.e., photopolymerization initiators, are preferred.
[0453] As photopolymerization initiators, a wide variety of compounds can be used without particular limitations. Examples of photopolymerization initiators include α-carbonyl compounds (as described in U.S. Patent Nos. 2,367,661 and 2,367,670), azobin ethers (as described in U.S. Patent No. 2,448,828), α-hydrocarbon-substituted aromatic azobin compounds (as described in U.S. Patent No. 2,722,512), polynuclear quinone compounds (as described in U.S. Patent Nos. 3,046,127 and 2,951,758), and combinations of triarylimidazolium dimers and p-aminophenyl ketones (as described in U.S. Patent No. 3,549,367). Specifications), acridine and phenazine compounds (Japanese Patent Application Publication No. 60-105667 and US Patent No. 4239850), oxadiazole compounds (US Patent No. 4212970), o-acyl oxime compounds (Japanese Patent Application Publication No. 2016-27384
[0065] ), and acylphosphine oxide compounds (Japanese Patent Application Publication No. 63-40799, Japanese Patent Application Publication No. 5-29234, Japanese Patent Application Publication No. 10-95788, and Japanese Patent Application Publication No. 10-29997), etc.
[0454] Commercially available products can also be used as photopolymerization initiators, such as IRGACURE-184, IRGACURE-907, IRGACURE-369, IRGACURE-651, IRGACURE-819, IRGACURE-OXE-01, and IRGACURE-OXE-02 manufactured by BASF.
[0455] When the liquid crystal composition contains a polymerization initiator, the content of the polymerization initiator relative to the total solid content of the liquid crystal composition is preferably 0.01 to 30% by mass, more preferably 0.1 to 15% by mass.
[0456] <Polymerizing compounds>
[0457] Liquid crystal compositions may contain polymeric compounds.
[0458] Examples of polymerizable compounds include compounds containing acrylates (e.g., (meth)acrylate monomers).
[0459] When the liquid crystal composition contains a polymerizable compound, the content of the polymerizable compound relative to the total solid content of the liquid crystal composition is preferably 0.5 to 50% by mass, more preferably 1.0 to 40% by mass.
[0460] <Surface Modifier>
[0461] Liquid crystal compositions may contain surface modifiers.
[0462] There are no particular restrictions on the use of surface modifiers; polymeric surface modifiers and low molecular weight surface modifiers can be used, as well as compounds described in paragraphs
[0253] to
[0293] of Japanese Patent Application Publication No. 2011-237513.
[0463] Furthermore, as a surface modifier, fluoro(meth)acrylate polymers described in
[0018] to
[0043] of Japanese Patent Application Publication No. 2007-272185 can also be used.
[0464] Furthermore, as a surface modifier, compounds described in paragraphs
[0079] to
[0102] of Japanese Patent Application Publication No. 2007-069471, polymerizable liquid crystal compounds represented by formula (4) described in Japanese Patent Application Publication No. 2013-047204 (especially compounds described in paragraphs
[0020] to
[0032] ), polymerizable liquid crystal compounds represented by formula (4) described in Japanese Patent Application Publication No. 2012-211306 (especially compounds described in paragraphs
[0022] to
[0029] ), and liquid crystal oriented compounds represented by formula (4) described in Japanese Patent Application Publication No. 2002-129162 can also be used. Accelerators (especially the compounds described in sections
[0076] to
[0078] and
[0082] to
[0084] ), compounds represented by formulas (4), (II) and (III) as described in Japanese Patent Application Publication No. 2005-099248 (especially the compounds described in sections
[0092] to
[0096] ), compounds described in sections
[0013] to
[0059] of Japanese Patent No. 4385997, compounds described in sections
[0018] to
[0044] of Japanese Patent No. 5034200, and compounds described in sections
[0019] to
[0038] of Japanese Patent No. 4895088.
[0465] A single surface modifier can be used alone, or two or more can be used simultaneously.
[0466] In this invention, considering the reason that the temperature dependence of the transmission axis center axis angle θ is reduced, the above-mentioned surface modifier is preferably an orientation agent that can set the phase transition reduction temperature ΔTB defined by the following formula (TB) to -10.0℃ to -0.1℃, and more preferably a surface modifier that can set the phase transition reduction temperature ΔTB defined by the following formula (TB) to -7.0℃ to -0.1℃.
[0467] ΔTB=TB1-TB2……(TB)
[0468] Here, in the above formula (TB), TB1 represents the phase transition temperature of the liquid and liquid crystal in a liquid crystal composition tb1 containing a thermotropic liquid crystal compound and a dichroic substance but without a surface modifier.
[0469] Furthermore, TB2 represents the phase transition temperature of the liquid and liquid crystal in a mixture tb2 containing 10.0 parts by mass of surface modifier relative to 100 parts by mass of the liquid crystal composition tb1 described above.
[0470] The detailed reason why the temperature dependence of the transmission axis center axis angle θ decreases when using a surface modifier that can set the phase transition reduction temperature ΔTB to -10.0℃ to -0.1℃ is not yet clear, but the inventors speculate as follows.
[0471] First, it is believed that the surface modifier is biased near the air interface of the light-absorbing anisotropic layer.
[0472] Furthermore, it is believed that the miscibility / immiscibility of liquid crystal compounds and dichroic substances with surface modifiers sometimes changes depending on temperature or liquid crystal phase transition, and due to this change, the tilt angle θ near the air interface changes.
[0473] Therefore, surface modifiers that can set the phase transition reduction temperature ΔTB to -10.0℃ to -0.1℃ have low affinity for liquid crystal compounds and dichroic substances and small temperature-induced changes in miscibility / immiscibility. Thus, it is believed that the temperature dependence of the transmission axis central axis angle θ is reduced.
[0474] The content of the surface modifier relative to the total solid content of the liquid crystal composition is preferably 0.005 to 15% by mass, more preferably 0.01 to 5% by mass, and even more preferably 0.015 to 3% by mass. When multiple surface modifiers are used simultaneously, the total amount of the multiple surface modifiers is preferably within the above range.
[0475] [Methods for forming anisotropic light-absorbing layers]
[0476] The method for forming the light-absorbing anisotropic layer of the present invention is not particularly limited, and a method comprising the following steps in sequence is given: a step of forming a coating film by coating the above-mentioned liquid crystal composition (hereinafter also referred to as "composition for forming a light-absorbing anisotropic layer") (hereinafter also referred to as "coating film forming step"); and a step of aligning the liquid crystal component or dichroic substance contained in the coating film (hereinafter also referred to as "alignment step").
[0477] Furthermore, when not only the aforementioned liquid crystal compounds but also the aforementioned dichroic substances possess liquid crystal properties, the liquid crystal component refers to a component that also contains dichroic substances possessing liquid crystal properties.
[0478] <Coating film formation process>
[0479] The coating film formation process is a process of forming a coating film by coating a light-absorbing anisotropic layer composition.
[0480] The light-absorbing anisotropic layer forming composition can be easily coated by using a composition containing the above-mentioned solvent or by using a liquid such as a melt prepared from the light-absorbing anisotropic layer forming composition by heating.
[0481] The coating method for the composition for forming anisotropic light-absorbing layers includes, for example, known methods such as roller coating, gravure printing, spin coating, wire rod coating, extrusion coating, direct gravure coating, reverse gravure coating, mold coating, spray coating, and inkjet coating.
[0482] <Orientation Process>
[0483] The alignment process is the process of orienting the liquid crystal components contained in the coated film. As a result, an anisotropic light absorption layer can be obtained.
[0484] The orientation process may include a drying process. The drying process removes components such as solvents from the coated film. The drying process can be performed by placing the coated film at room temperature for a specified time (e.g., natural drying), or by heating and / or air supply.
[0485] Here, the liquid crystal component contained in the composition for forming anisotropic light absorption layers is sometimes oriented through the above-described coating film forming process or drying process. For example, in the method of preparing a coating liquid containing a solvent from the composition for forming anisotropic light absorption layers, a coating film having anisotropic light absorption (i.e., anisotropic light absorption layer) can be obtained by drying the coating film to remove the solvent from the coating film.
[0486] When drying is performed at a temperature above the transition temperature of the liquid crystal component contained in the coated film to the liquid crystal phase, the heating treatment described later may be omitted.
[0487] From a manufacturing suitability perspective, the transition temperature of the liquid crystal component in the coating film to the liquid crystal phase is preferably 10–250°C, more preferably 25–190°C. If the transition temperature is 10°C or higher, cooling processes to lower the temperature to the display liquid crystal phase's temperature range are unnecessary, which is therefore preferable. Furthermore, if the transition temperature is 250°C or lower, even when temporarily set to an isotropic liquid state at a temperature higher than the display liquid crystal phase's temperature range, high temperatures are not required, thereby reducing heat energy waste, substrate deformation, and deterioration, which is also preferable.
[0488] The alignment process preferably includes a heat treatment. This allows the liquid crystal components contained in the coated film to be aligned, thus enabling the heat-treated coated film to be preferably used as a light-absorbing anisotropic layer.
[0489] From the perspective of manufacturing applicability, the heat treatment is preferably 10–250°C, more preferably 25–190°C. Furthermore, the heating time is preferably 1–300 seconds, more preferably 1–60 seconds.
[0490] The alignment process may include a cooling process performed after the heat treatment. The cooling process involves cooling the heated coating film to room temperature (20–25°C). This helps to fix the alignment of the liquid crystal components contained in the coating film. There is no particular limitation on the cooling method; it can be implemented using known methods.
[0491] Through the above processes, an anisotropic light absorption layer can be obtained.
[0492] In addition, in this method, drying treatment and heat treatment can be cited as methods for aligning the liquid crystal components contained in the coating film, but it is not limited to these, and can be implemented by known alignment treatments.
[0493] <Other processes>
[0494] The method for forming the light-absorbing anisotropic layer may include a step of curing the light-absorbing anisotropic layer (hereinafter also referred to as the "curing step") after the above-mentioned orientation step.
[0495] For example, when the light-absorbing anisotropic layer has cross-linking groups (polymeric groups), the curing process is carried out by heating and / or light irradiation (exposure). Preferably, the curing process is carried out by light irradiation.
[0496] The light source used for curing can be various types of light sources such as infrared, visible, or ultraviolet light, with ultraviolet light being preferred. Furthermore, curing can be performed by heating while simultaneously irradiating with ultraviolet light, or by irradiating with ultraviolet light through a filter that allows only specific wavelengths to pass through.
[0497] When heating and exposure are performed simultaneously, the heating temperature during exposure also depends on the transition temperature of the liquid crystal components contained in the liquid crystal film to the liquid crystal phase, but it is preferably 25 to 140°C.
[0498] Furthermore, exposure can be performed under a nitrogen atmosphere. Since the curing of the liquid crystal film via free radical polymerization reduces the hindrance to polymerization caused by oxygen, exposure under a nitrogen atmosphere is preferred.
[0499] The thickness of the light-absorbing anisotropic layer of the present invention is not particularly limited, but from the viewpoint of miniaturization and lightweighting, it is preferably 100 to 8000 nm, and more preferably 300 to 5000 nm.
[0500] Patterning of anisotropic light absorption layers
[0501] The light-absorbing anisotropic layer of the present invention can be configured as a light-absorbing anisotropic layer having regions A and B in the plane, with different transmittance central axes in each region. By controlling the light-emitting pixels by patterning each pixel of the liquid crystal, it is possible to switch the center of view in a narrow field of view.
[0502] Furthermore, the light-absorbing anisotropic layer of the present invention can be a light-absorbing anisotropic layer with different transmittances, which are inclined at 30° from the transmittance central axis along the normal direction in a plane having regions C and D in the plane, and regions C and D containing the transmittance central axis and the normal direction of the surface of the light-absorbing anisotropic layer. In this case, it is preferable that the transmittance of region C, which is inclined at 30° from the transmittance central axis along the normal direction, is 50% or less, and the transmittance of region D, which is inclined at 30° from the transmittance central axis along the normal direction, is 80% or more.
[0503] By performing the aforementioned patterning, viewing angle dependence can be enhanced or reduced in localized areas. This allows highly confidential information to be displayed only in areas where viewing angle dependence is enhanced. Furthermore, controlling viewing angle dependence at each display position allows for a design with excellent aesthetics. Moreover, by controlling the luminescent pixels through patterning each pixel of the liquid crystal, switching between narrow and wide viewing angles is possible.
[0504] <Pattern Formation Methods>
[0505] Therefore, there are no limitations on the method for forming a patterned light-absorbing anisotropic layer having two or more different regions within the plane. For example, various known methods as described in WO2019 / 176918 can be used. As examples, methods for forming a pattern by changing the irradiation angle of ultraviolet light irradiating the photo-alignment film, methods for controlling the thickness of the patterned light-absorbing anisotropic layer within the plane, methods for biasing dichroic pigment compounds in the patterned light-absorbing anisotropic layer, and methods for post-processing an optically uniform patterned light-absorbing anisotropic layer are also mentioned.
[0506] Methods for controlling the thickness of an in-plane patterned anisotropic light absorption layer include photolithography, imprinting, and forming the patterned anisotropic light absorption layer on a substrate with an uneven structure. Methods for dispersing dichroic pigment compounds in the patterned anisotropic light absorption layer include solvent impregnation extraction of dichroic pigments (bleaching). Furthermore, methods for post-processing the optically uniform patterned anisotropic light absorption layer include cutting a portion of the flattened layer using laser processing or similar methods.
[0507] [Optical film]
[0508] The optical film of the present invention has the light absorption anisotropic layer of the present invention described above and an orientation film made of polyvinyl alcohol or polyimide disposed on the light absorption anisotropic layer described above.
[0509] Furthermore, the optical film of the present invention may have a transparent film substrate on the side of the alignment film opposite to the light absorption anisotropic layer.
[0510] The components constituting the optical film of the present invention will be described below.
[0511] [Light Absorption Anisotropic Layer]
[0512] The light absorption anisotropic layer of the optical film of the present invention is the light absorption anisotropic layer of the present invention described above, therefore its description is omitted.
[0513] [Orientation film]
[0514] The optical film of the present invention has an alignment film composed of polyvinyl alcohol or polyimide.
[0515] Regarding the alignment film, please refer to the description on page 43, line 24 to page 49, line 8 of International Publication No. 2001 / 88574A1.
[0516] The thickness of the alignment film is preferably 0.01 to 10 μm, more preferably 0.01 to 1 μm.
[0517] [Transparent film substrate]
[0518] As a transparent film substrate, known transparent resin films, transparent resin sheets, transparent resin plates, etc., can be used, without particular limitation. As a transparent resin film, cellulose acylate films (e.g., cellulose triacetate films (refractive index 1.48), cellulose diacetate films, cellulose acetate butyrate films, cellulose acetate propionate films), polyethylene terephthalate films, polyethersulfone films, polyacrylic acid resin films, polyurethane resin films, polyester films, polycarbonate films, polysulfone films, polyether films, polymethylpentene films, polyetherketone films, (meth)acrylonitrile films, etc., can be used.
[0519] The preferred material is a cellulose acylate film, which has high transparency, low optical birefringence, is easy to manufacture, and is commonly used as a protective film for polarizers. Cellulose triacetate film is particularly preferred.
[0520] The thickness of the transparent film substrate is typically 20μm to 100μm.
[0521] In this invention, it is particularly preferred that the transparent film substrate is a cellulose ester film with a film thickness of 20 to 70 μm.
[0522] [Blocking layer]
[0523] The optical film of the present invention preferably comprises a transparent film substrate, a light-absorbing anisotropic layer, and a blocking layer.
[0524] Here, the barrier layer is also called the gas barrier layer (oxygen barrier layer), which has the function of protecting the polarization element of the present invention from the influence of gases such as oxygen in the atmosphere, moisture or compounds contained in adjacent layers.
[0525] Regarding the barrier layer, for example, reference can be made to paragraphs
[0014] to
[0054] of Japanese Patent Application Publication No. 2014-159124, paragraphs
[0042] to
[0075] of Japanese Patent Application Publication No. 2017-121721, paragraphs
[0045] to
[0054] of Japanese Patent Application Publication No. 2017-115076, paragraphs
[0010] to
[0061] of Japanese Patent Application Publication No. 2012-213938, and paragraphs
[0021] to
[0031] of Japanese Patent Application Publication No. 2005-169994.
[0526] [Refractive index adjustment layer]
[0527] From the viewpoint of suppressing the effect of internal reflection caused by the high refractive index of the light-absorbing anisotropic layer, the optical film of the present invention preferably has a refractive index adjustment layer.
[0528] The refractive index adjustment layer is a layer configured to be in contact with the light-absorbing anisotropic layer, and has an in-plane average refractive index of 1.55 or higher and 1.70 or lower at a wavelength of 550 nm. Preferably, it is a refractive index adjustment layer used for so-called refractive index matching.
[0529] [View Control System]
[0530] The viewing angle control system of the present invention has a polarizer having an absorption axis in the in-plane direction and the light absorption anisotropic layer of the present invention or the optical film of the present invention.
[0531] [Polarizer]
[0532] The polarizer in the viewing angle control system of the present invention is not particularly limited as long as it is a component that has an absorption axis in the plane and has the function of converting light into specific linearly polarized light, and conventionally known polarizers can be used.
[0533] As a polarizer, iodine-based polarizers, dye-based polarizers utilizing dichroic dyes, and polyene-based polarizers can be used. Iodine-based and dye-based polarizers include both coated and stretched types. As a coated polarizer, a polarizer that orients dichroic organic pigments by utilizing the orientation of a liquid crystal compound is preferred. As a stretched polarizer, a polarizer made by adsorbing iodine or a dichroic dye onto polyvinyl alcohol and then stretching it is preferred.
[0534] Furthermore, as a method for obtaining a polarizer by stretching and dyeing a laminated film in which a polyvinyl alcohol layer is formed on a substrate, examples include Japanese Patent No. 5048120, Japanese Patent No. 5143918, Japanese Patent No. 5048120, Japanese Patent No. 4691205, Japanese Patent No. 4751481, and Japanese Patent No. 4751486, and known techniques related to these polarizers can be preferred.
[0535] From the perspective of easy availability and excellent polarization, a polarizer comprising a polyvinyl alcohol resin (a polymer containing -CH2-CHOH- as repeating units. In particular, a polarizer selected from at least one of the groups comprising polyvinyl alcohol and ethylene-vinyl alcohol copolymers) is preferred.
[0536] In this invention, the thickness of the polarizer is not particularly limited, but is preferably 3μm to 60μm, more preferably 5μm to 20μm, and even more preferably 5μm to 10μm.
[0537] In the viewing angle control system of the present invention, the angle φ formed by the direction φ1 of projecting the transmittance center of the light-absorbing anisotropic layer onto the film surface and the absorption axis φ2 of the polarizer is preferably 45° to 90°, more preferably 80° to 90°, and even more preferably 88° to 90°. The closer the angle is to 90°, the better it can impart illuminance contrast between the easily observable and difficult-to-observe directions to the image display device.
[0538] The viewing angle control system of the present invention can be stacked with the light absorption anisotropic layer and the polarizer via an adhesive layer or bonding layer described later, or the alignment film and the light absorption anisotropic layer can be directly coated on the polarizer for stacking.
[0539] [Adhesive layer]
[0540] The adhesive layer is preferably a transparent and optically isotropic adhesive, similar to the adhesive layers used in conventional image display devices, and pressure-sensitive adhesives are typically used.
[0541] In addition to the base material (adhesive), conductive particles, and thermally expanding particles as needed, the adhesive layer may also contain appropriate additives such as crosslinking agents (e.g., isocyanate crosslinking agents, epoxy crosslinking agents, etc.), tackifiers (e.g., rosin derivative resins, polyterpene resins, petroleum resins, oil-soluble phenolic resins, etc.), plasticizers, fillers, anti-aging agents, surfactants, ultraviolet absorbers, light stabilizers, and antioxidants.
[0542] The thickness of the adhesive layer is typically 20–500 μm, preferably 20–250 μm. When it is less than 20 μm, the required adhesive strength or reprocessability may not be obtained, and when it exceeds 500 μm, the adhesive may sometimes protrude or seep out from the peripheral end of the image display device.
[0543] When forming the adhesive layer, it can be done by, for example, by the following appropriate methods: directly applying the base material, conductive particles and coating liquid containing thermally expanding particles, additives, solvents, etc. as needed onto the support 110 for the protective component and pressing it through a release liner; or applying the coating liquid onto a suitable release liner (release paper, etc.) to form a thermally expanding adhesive layer and pressing it onto the support 110 for the protective component.
[0544] In addition, as a protective component, a structure can be formed by adding conductive particles to the structure of the heat-peelable adhesive sheet described in Japanese Patent Application Publication No. 2003-292916.
[0545] Furthermore, as a protective component, a component made by spreading conductive particles on the surface of the adhesive layer of commercially available products such as "REVALPHA" manufactured by Nitto Denko Corporat ion can be used.
[0546] [Adhesive layer]
[0547] Adhesives exhibit their adhesive properties through drying or reaction after bonding.
[0548] Polyvinyl alcohol adhesives (PVA adhesives) exhibit adhesive properties upon drying, enabling them to bond materials together.
[0549] Specific examples of curing adhesives that exhibit adhesion through reaction include active energy radiation-curing adhesives such as (meth)acrylate adhesives and cationic polymerization-curing adhesives. Furthermore, (meth)acrylate refers to acrylates and / or methacrylates. As curing components in (meth)acrylate-based adhesives, examples include compounds having (meth)acryloyl groups and compounds having vinyl groups. Furthermore, as cationic polymerization-curing adhesives, compounds having epoxy groups or oxobutyl groups can also be used. There are no particular limitations on compounds having at least two epoxy groups within the molecule; various commonly known curing epoxy compounds can be used. Preferred epoxy compounds include compounds having at least two epoxy groups and at least one aromatic ring within the molecule (aromatic epoxy compounds), or compounds having at least two epoxy groups within the molecule, with at least one formed between two adjacent carbon atoms constituting an alicyclic ring (alicyclic epoxy compounds).
[0550] From the perspective of heat deformation resistance, UV-curable adhesives that are cured by UV irradiation are preferred.
[0551] The adhesive layer and its layers can be layers that are endowed with ultraviolet absorption capabilities by means of ultraviolet absorbers such as salicylate compounds, benzophenol compounds, benzotriazole compounds, cyanoacrylate compounds, and nickel complex salt compounds.
[0552] The application of the adhesive layer and bonding layer can be carried out in a suitable manner. For example, the following methods can be used: preparing an adhesive solution of about 10 to 40% by weight, which is made by dissolving or dispersing the matrix polymer or a composition thereof in a solvent consisting of a single substance or mixture of suitable solvents such as toluene or ethyl acetate, and directly applying it to the film by a suitable spreading method such as casting or coating, or forming an adhesive layer on the separator as described above and then transferring it thereon.
[0553] Adhesive layers and bonding layers can also be disposed on one or both sides of the membrane as overlapping layers of different compositions or types. Furthermore, when disposed on both sides, adhesive layers of different compositions, types, or thicknesses can be disposed on the surface and back of the membrane.
[0554] [Other layers]
[0555] In order to control the angle dependence of the viewing angle, the viewing angle control system of the present invention can further combine the above-mentioned light absorption anisotropic layer with an optical anisotropic film or polarizer. For example, as a transparent substrate film, a resin film with optical anisotropy composed of polymers including carbonates, cycloolefins, cellulose acylates, methyl methacrylate, styrene, maleic anhydride, etc. is preferably used.
[0556] [Image display device]
[0557] The image display device of the present invention includes a display element and the viewing angle control system of the present invention described above. The viewing angle control system is an image display device disposed on at least one main surface of the display element.
[0558] Furthermore, the image display device of the present invention is preferably an image display device in which the light absorption anisotropic layer of the viewing angle control system is disposed on the visual recognition side further away from the polarizer of the viewing angle control system, that is, an image display device having the light absorption anisotropic layer, the polarizer and the display element in sequence from the visual recognition side.
[0559] The display element used in the image display device of the present invention is not particularly limited, and examples include liquid crystal cells, organic electroluminescent (hereinafter referred to as "EL") display panels and plasma display panels.
[0560] Preferably, a liquid crystal cell or an organic EL display panel is used. That is, as the display device of the present invention, a liquid crystal display device using a liquid crystal cell as a display element or an organic EL display device using an organic EL display panel as a display element is preferred.
[0561] Image display devices include thin image display devices that can be formed on curved surfaces. The optical anisotropic absorption film used in this invention is thin and easily bent, and therefore is also preferably suitable for image display devices with curved display surfaces.
[0562] Furthermore, there are image display devices with pixel densities exceeding 250 ppi that are capable of high-definition display. The optical anisotropic absorption film used in this invention is also preferably suitable for such high-definition image display devices without generating interference ripples.
[0563] [Liquid Crystal Display Device]
[0564] As an example of the display device of the present invention, a liquid crystal display device is preferably provided that has an optical film having the above-described polarizer and a liquid crystal cell.
[0565] As a specific structure, there are configurations in which the optical film of the present invention is disposed on a front polarizer or a rear polarizer. In these configurations, the viewing angle that is blocked in the vertical or horizontal direction can be controlled.
[0566] Furthermore, the optical film of the present invention can be disposed on both the front polarizer and the rear polarizer. By setting it in this way, viewing angle control can be achieved, where light is blocked from all directions and only transmitted from the front.
[0567] Furthermore, multiple optical films of the present invention can be stacked via a phase retardation layer. By controlling the phase difference value and the optical axis direction, the transmission performance and light-blocking performance can be controlled. For example, by arranging a polarizer, an optical film, a λ / 2 wavelength plate (the axis angle being an angle deviating 45° from the orientation direction of the polarizer), and an optical film, viewing angle control that allows light to be blocked from all directions and transmitted only in the front direction can be achieved. As the phase retardation layer, a positive A plate, a negative A plate, a positive C plate, a negative C plate, a B plate, an O plate, etc., can be used. From the viewpoint of making the viewing angle control system thinner, the thickness of the phase retardation layer is preferably thinner without impairing optical properties, mechanical properties, and manufacturing applicability. Specifically, it is preferably 1 to 150 μm, more preferably 1 to 70 μm, and even more preferably 1 to 30 μm.
[0568] The liquid crystal unit constituting a liquid crystal display device will now be described in detail.
[0569] <Liquid Crystal Unit>
[0570] The liquid crystal cells used in the liquid crystal display device are preferably in VA (Vertical Alignment) mode, OCB (Optically Compensated Bend) mode, IPS (In-Plane-Switching) mode or TN (Twisted Nematic) mode, but are not limited to these.
[0571] In TN mode liquid crystal cells, the rod-shaped liquid crystal molecules are essentially horizontally oriented when no voltage is applied, and then twisted to an orientation of 60–120°. TN mode liquid crystal cells are most commonly used in color TFT liquid crystal display devices and are documented in most literature.
[0572] In a VA-mode liquid crystal cell, the rod-shaped liquid crystal molecules are substantially vertically oriented when no voltage is applied. VA-mode liquid crystal cells include (1) a narrow definition of a VA-mode liquid crystal cell in which the rod-shaped liquid crystal molecules are substantially vertically oriented when no voltage is applied and substantially horizontally oriented when a voltage is applied (described in Japanese Patent Application Publication No. 2-176625), as well as (2) a liquid crystal cell in which the VA mode is multi-domained to expand the viewing angle (MVA mode) (described in SID97, Digest of Tech. Papers 28 (1997) 845), (3) a liquid crystal cell in which the rod-shaped liquid crystal molecules are substantially vertically oriented when no voltage is applied and twisted into multi-domain orientation when a voltage is applied (n-ASM mode) (described in the proceedings of the Japan Liquid Crystal Conference 58-59 (1998)), and (4) a SURVIVAL mode liquid crystal cell (published in LCD International 98). Furthermore, it can be any of the following types: PVA (Patterned Vertical Alignment), Optical Alignment, and PSA (Polymer-Sustained Alignment). Detailed information about these types can be found in Japanese Patent Application Publication Nos. 2006-215326 and 2008-538819.
[0573] In IPS mode liquid crystal cells, the liquid crystal compound is substantially parallel to the substrate, and the liquid crystal molecules respond planarly when an electric field parallel to the substrate surface is applied. That is, in the state where no electric field is applied, the liquid crystal compound is oriented in-plane. In the IPS mode, black is displayed in the state where no electric field is applied, and the absorption axes of the upper and lower pairs of polarizers are orthogonal to each other. Japanese Patent Application Publication Nos. 10-54982, 11-202323, 9-292522, 11-133408, 11-305217, and 10-307291 disclose a method for reducing light leakage and improving viewing angle when displaying black in the tilt direction using an optical compensation sheet.
[0574] [Organic EL display device]
[0575] As an example of the display device of the present invention, an organic EL display device may preferably be provided in a manner in which an optical film having the above-mentioned polarizer, an ingress / outgress plate, and an organic EL display panel are sequentially arranged from the visual recognition side.
[0576] Furthermore, similar to the liquid crystal display device described above, multiple optical films of the present invention can be stacked via a phase retardation layer and disposed on an organic EL display panel. By controlling the phase retardation value and the optical axis direction, the transmission performance and light-shielding performance can be controlled.
[0577] Furthermore, the organic EL display panel is a display panel made of organic EL elements formed by sandwiching an organic light-emitting layer (organic electroluminescent layer) between electrodes (between the cathode and the anode). There are no particular restrictions on the structure of the organic EL display panel, and known structures can be used.
[0578] Example
[0579] The present invention will now be described in further detail with reference to embodiments. The materials, amounts, proportions, processing contents, and processing order shown in the following embodiments can be appropriately modified without departing from the spirit of the invention. Therefore, the scope of the invention should not be limited by the embodiments shown below.
[0580] [Example 1]
[0581] <Formation of Orientation Film 1>
[0582] The surface of cellulose acylated membrane 1 (a 40 μm thick TAC substrate; TG40 FUJIFILM Co., Ltd.) was saponified with an alkaline solution, and the following coating solution for forming an orientation film was applied to it using a wire rod. The coated cellulose acylated membrane 1 was dried with warm air at 60°C for 60 seconds, and then further dried with warm air at 100°C for 120 seconds to form an orientation film 1, thereby obtaining a TAC membrane with an orientation film.
[0583] The film thickness is 0.5 μm.
[0584] Furthermore, the TAC membrane with the orientation film produced is used after the orientation film surface is rubbed.
[0585]
[0586] Modified polyvinyl alcohol
[0587] [Chemical Formula 30]
[0588]
[0589] <Fabrication of anisotropic light-absorbing layers>
[0590] The following light-absorbing anisotropic layer forming composition P1 was applied to the orientation film of the prepared TAC film with an orientation film using a wire rod, thereby forming a coating layer P1.
[0591] Next, the coating layer P1 is heated at 120°C for 30 seconds and then cooled to 100°C.
[0592] Then, using an LED (Light Emitting Diode) lamp (center wavelength 365nm), at room temperature (25℃) and an illuminance of 200mW / cm², 2 Irradiation for 2 seconds under the specified irradiation conditions resulted in the fabrication of a light-absorbing anisotropic layer P1-A on the alignment film 1.
[0593] In the same manner, coating layer P1 was heated at 120°C for 30 seconds and then cooled to 70°C. An LED lamp (center wavelength 365nm) was used at room temperature (25°C) and an illuminance of 200mW / cm². 2 Irradiation for 2 seconds under the specified irradiation conditions resulted in the fabrication of a light-absorbing anisotropic layer P1-B on the alignment film 1.
[0594] The thickness of both the light-absorbing anisotropic layer P1-A and the light-absorbing anisotropic layer P1-B is 2.1 μm.
[0595]
[0596] <Phase transition temperature decrease (ΔTF)>
[0597] The two linear polarizers of the optical microscope (manufactured by Nikon Corporation, product name "ECLIPSE E600 POL") were set to have their absorption axes orthogonal.
[0598] A dichloromethane solution of the following composition P1' was cast onto a glass slide and placed on a sample stage positioned between two linear polarizers. The slide was then placed at 70°C for 30 minutes to allow the solvent to dry. The slide was then heated for 5 seconds using a hot plate at a temperature 5°C higher than the liquid-to-liquid phase transition temperature. The temperature at which the liquid phase transitioned to the liquid crystal phase (T2) was determined while the slide was cooled at a rate of 5°C / min.
[0599] Similarly, using the composition from which the orientation agent was removed from composition P1', the temperature (T1) at which the liquid phase transitioned to the liquid crystal phase was determined in the same manner, and ΔTF = T1 - T2 was calculated.
[0600]
[0601] <Transmittance center axis angle θ>
[0602] A 4cm × 4cm sample was taken from the fabricated anisotropic light-absorbing layer P1-A and cut out. The cut sample was placed on a JASCO V-670 / ARMN-735 (manufactured by JASCO Corporation) with the direction φ1, in which the center of transmittance is orthographically projected onto the film surface, horizontal. The transmittance T3-A was measured in the range of θ = -75° to 75° while changing the polar angle at intervals of 0.5° with linearly polarized light vibrating in the horizontal direction at 650 nm relative to the film.
[0603] In the same manner, the transmittance T3-B of the light-absorbing anisotropic layer P1-B was measured.
[0604] The transmittance T4 of the TAC film with the orientation film was further measured and T3-A / T4 was calculated. The angle with the largest value was used as the angle θA of the transmittance center axis.
[0605] Similarly, T3-B / T4 was calculated, and the angle with the largest value was used as the angle θB of the transmittance center axis. The results were evaluated according to the following criteria. The results are shown in Table 1 below.
[0606] A: θB is greater than 5° and less than 35°
[0607] B: θB is greater than 35° and less than 45°
[0608] C: θB is greater than 45° and less than 80°
[0609] D: θB is greater than 0° and less than 5° or greater than 80°
[0610] <Temperature dependence of transmittance central axis angle θ>
[0611] The absolute value Δθ, the difference between θA and θB measured at the transmittance center axis angle θ, was calculated and evaluated according to the following criteria. The results are shown in Table 1 below.
[0612] A: Δθ is less than 7°
[0613] B: Δθ is 7° or higher and less than 12°
[0614] C: Δθ is 12° or more
[0615] <Ratio of transmittance>
[0616] Using the same method as for determining the central axis angle θ of transmittance, the maximum and minimum transmittance values Tmax and Tmin were measured using the light absorption anisotropic layer P1-B. The ratio of transmittance, Tc = Tmax / Tmin, was calculated and evaluated according to the following criteria. The results are shown in Table 1 below.
[0617] A: Tc is above 150
[0618] B: Tc is 100 or higher and less than 150
[0619] C: Tc is 40 or higher and less than 100
[0620] D: Tc is 20 or higher and less than 40
[0621] E: Tc is less than 20
[0622] [Examples 2-7 and Comparative Examples 1-2]
[0623] The composition of the light absorption anisotropic layer forming composition P1 was changed to the composition shown in Table 1 below. Otherwise, the light absorption anisotropic layers of Examples 2 to 7 and Comparative Examples 1 to 2 were produced in the same manner as in Example 1.
[0624] For the fabricated anisotropic light-absorbing layer, the phase transition temperature drop (ΔTF), the temperature dependence of the transmittance central axis angle θ, and the transmittance ratio were evaluated using the same method as in Example 1. The results are shown in Table 1 below.
[0625]
[0626] The components indicated by symbols in Table 1 above are shown below. Additionally, the values in parentheses for each repeating unit indicate the content (mass %) of each repeating unit relative to all repeating units present in each polymer.
[0627] Liquid crystal compound L1
[0628] [Chemical Formula 31]
[0629]
[0630] Liquid crystal compound L2
[0631] [Chemical Formula 32]
[0632]
[0633] Liquid crystal compound L3
[0634] [Chemical Formula 33]
[0635]
[0636] Liquid crystal compound L4
[0637] [Chemical Formula 34]
[0638]
[0639] Dichroic substance Y1
[0640] [Chemical Formula 35]
[0641]
[0642] Dichroic substance Y2
[0643] [Chemical Formula 36]
[0644]
[0645] Dichroic substance M1
[0646] [Chemical Formula 37]
[0647]
[0648] Dichroic substance M2
[0649] [Chemical Formula 38]
[0650]
[0651] dichroic substance C1
[0652] [Chemical Formula 39]
[0653]
[0654] dichroic substance C2
[0655] [Chemical Formula 40]
[0656]
[0657] dichroic substance C3
[0658] [Chemical Formula 41]
[0659]
[0660] Surface Modifier B1
[0661] [Chemical Formula 42]
[0662]
[0663] Orientation agent F1
[0664] [Chemical Formula 43]
[0665]
[0666] Orientation agent F2
[0667] [Chemical Formula 44]
[0668]
[0669] Orientation agent F3
[0670] [Chemical Formula 45]
[0671]
[0672] Orientation agent F4
[0673] [Chemical Formula 46]
[0674]
[0675] Orientation agent F5
[0676] [Chemical Formula 47]
[0677]
[0678] According to the results shown in Table 1, when the content of dichroic material is less than 8.0% by mass relative to the total solid content of the liquid crystal composition and the transmittance center axis angle θ is 45° or more, the transmittance ratio (Tc = Tmax / Tmin) becomes lower. Therefore, when viewed from the direction where the image is to be seen (the desired direction), the image cannot be sufficiently visually recognized, and when viewed from other directions, the image cannot be sufficiently obscured (Comparative Example 1).
[0679] Furthermore, it is known that even if the content of dichroic material is 8.0% or more of the total solid content of the liquid crystal composition, if the transmittance center axis angle θ is less than 5°, the transmittance ratio (Tc = Tmax / Tmin) becomes lower. Therefore, when viewed from the direction in which the image is to be seen (the desired direction), the image cannot be sufficiently visually recognized, and when viewed from other directions, the image cannot be sufficiently obscured (Comparative Example 2).
[0680] In contrast, it can be seen that when the content of dichroic material is 8.0% or more by mass relative to the total solid content of the liquid crystal composition and the transmittance center axis angle θ is 5° or more and less than 80°, the transmittance ratio (Tc = Tmax / Tmin) becomes higher, the visual recognition of the image from the desired direction is high, and the image from other directions can be sufficiently blocked (Examples 1 to 7).
[0681] In particular, a comparison between Example 1 and Example 2 shows that when the content of the dichroic substance is 13.0% by mass or more of the total solid content of the liquid crystal composition, the transmittance ratio (Tc = Tmax / Tmin) becomes higher.
[0682] Furthermore, a comparison between Example 3 and Example 6 shows that when an orientation agent capable of setting the phase transition reduction temperature ΔTF to -10.0℃ to -0.1℃ is formulated, the temperature dependence of the transmittance center angle θ is improved and the transmittance ratio (Tc = Tmax / Tmin) becomes higher.
[0683] Furthermore, based on the comparison between Example 4 and Example 6, it can be seen that when the content of the orientation agent satisfies the above formula (C) [0.010≤Ct / FT≤0.020], the transmittance ratio (Tc=Tmax / Tmin) becomes higher.
[0684] Furthermore, a comparison between Example 5 and Example 6 shows that when the orientation agent is a compound represented by the above formula (B1) or (B2), the transmittance ratio (Tc = Tmax / Tmin) becomes higher.
Claims
1. A light-absorbing anisotropic layer, formed of a liquid crystal composition containing a liquid crystal compound, a dichroic substance, and an alignment agent, wherein, The content of the dichroic substance is 8.0% to 50% by mass relative to the total solid content of the liquid crystal composition. The angle θ between the transmittance central axis of the light-absorbing anisotropic layer and the normal direction of the surface of the light-absorbing anisotropic layer is greater than 5° and less than 80°. The orientation agent is an orientation agent capable of setting the phase transition reduction temperature ΔTF, as defined by the following formula (TF), to -10.0℃ to -0.1℃. ΔTF = T1 - T2 (TF) Here, in the formula (TF), T1 represents the phase transition temperature of the liquid and liquid crystal in a liquid crystal composition t1 containing a thermotropic liquid crystal compound and a dichroic substance but without an alignment agent. T2 represents the phase transition temperature of the liquid and the liquid crystal in the mixture t2, which contains 2.0 parts by mass of alignment agent relative to 100 parts by mass of the liquid crystal composition t1.
2. The light-absorbing anisotropic layer according to claim 1, wherein, The content of the dichroic substance is 13.0% to 50% by mass relative to the total solid content of the liquid crystal composition.
3. The light-absorbing anisotropic layer according to claim 1, wherein, The liquid crystal compound is a liquid crystal compound that exhibits thermotropic properties.
4. The light-absorbing anisotropic layer according to claim 1, wherein, The content of the orientation agent satisfies the following formula (C). 0.010≤Ct / FT≤0.020 (C) Here, in the above equation (C), Ct represents the content of the alignment agent relative to the total solid content of the liquid crystal composition, expressed as % by mass. FT represents the film thickness of the light-absorbing anisotropic layer, in μm.
5. The light-absorbing anisotropic layer according to claim 1, wherein, The orientation agent is a compound represented by the following formula (B1) or (B2). Here, in equations (B1) and (B2), Ring A represents a quaternary ammonium ion formed from a nitrogen-containing heterocycle. X represents anion. L 1 Indicates a bivalent linker. L 2 Indicates a single bond or a binary linker. Y 1 This indicates a divalent linker with a 5- or 6-membered ring as part of the structure. Z indicates that an alkylene group with 2 to 20 carbon atoms serves as a divalent linker in part of the structure. P 1 and P 2 Each of these can be independently represented as a monovalent substituent having a polymerizable olefinic unsaturated bond. R 1 and R 2 Each of these can be independently represented as a hydrogen atom, an aliphatic hydrocarbon group with or without substituents, an aryl group with or without substituents, or a heterocyclic group with or without substituents. R 3 Indicates a substituent.
6. An optical film comprising a light-absorbing anisotropic layer according to any one of claims 1 to 5, and an orientation film formed of polyvinyl alcohol or polyimide disposed on the light-absorbing anisotropic layer.
7. A viewing angle control system comprising a polarizer having an absorption axis in an in-plane direction, and a light-absorbing anisotropic layer according to any one of claims 1 to 5 or an optical film according to claim 6.
8. An image display device comprising a display element and a viewing angle control system as described in claim 7. The viewing angle control system is configured on at least one main surface of the display element.
9. The image display device according to claim 8, wherein, The light absorption anisotropic layer of the view control system is positioned further toward the visual recognition side than the polarizer of the view control system.
Citation Information
Patent Citations
JP1973095088A
JP1975034200A
JP1975048120A
Irokeshitaibutsurenzu
JP1976043918A
Photosensitive compound containing trichloromethyl group, manufacture and photosensitive mixture
JP1985105667A